Biaxially oriented polyester film, laminate, and packaging container
By using chemically recycled polyester and controlling its molecular weight distribution, the problem of high low molecular weight components in recycled polyester is solved, and the yellowness of the film is reduced and the tensile stability is improved.
Patent Information
- Application Number
- CN202380056415.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-29
- Filing Date
- 2023-01-30
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The used PET plastic bottles are difficult to completely remove contaminants during mechanical recycling, resulting in the recycled polyester containing more low molecular weight components, the product is prone to yellow color, and easily break when stretched.
Chemical recycling of polyester is used, and by controlling its molecular weight distribution, the area ratio of the area below 1000 is more than 1.9% but not more than 5.5%, so as to reduce the content of low molecular weight components, reduce yellowing, and improve the stretch stability of the film.
It effectively reduces the environmental burden, reduces the yellowness of the film, improves the stability of the film during the stretching process, and reduces the risk of fracture.
Smart Images

Figure CN119604565A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to biaxially oriented polyester films, laminates and packaging containers. Background Art
[0002] Polyesters such as polyethylene terephthalate (PET) and polybutylene terephthalate (PBT), which are thermoplastic resins with excellent heat resistance and mechanical properties, are used in a wide variety of fields, including plastic films, electronic technology, energy, packaging materials, and automobiles. Among them, biaxially oriented polyester films are widely used in industrial and packaging applications because of their excellent balance between mechanical strength (i.e., mechanical properties), heat resistance, dimensional stability, chemical resistance, optical properties, and cost.
[0003] In recent years, as the call for building a recycling-oriented society has grown, the use of recycled raw materials has been promoted in the field of materials. For polyester, used PET plastic bottles are also recycled. It is said that the use of recycled polyester can help reduce CO2. In this case, it is expected to increase the use rate of recycled polyester as much as possible.
[0004] For example, Patent Document 1 discloses a biaxially oriented polyester film produced using polyester obtained by mechanically recycling PET plastic bottles, that is, mechanically recycled polyester.
[0005] However, since the degree of contamination of used polyester products such as used PET plastic bottles varies depending on the contents filled therein, the storage environment, etc., it is difficult to remove contaminants to a high degree in mechanical recycling.
[0006] On this basis, mechanically recycled polyester contains a large amount of low molecular weight components, and therefore, products made using mechanically recycled polyester sometimes appear yellow.
[0007] However, as polyester recycled by a method different from mechanical recycling, there is known a polyester obtained by decomposing polyester contained in a used polyester product to a monomer level and polymerizing it again, namely, chemically recycled polyester (see Patent Documents 3 and 4).
[0008] For example, Patent Document 2 discloses a printed resin film including a polyester film produced using chemically recycled polyester and a printed layer.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent No. 6036099
[0012] Patent Document 2: Japanese Patent No. 6984717
[0013] Patent Document 3: Japanese Patent Application Publication No. 2000-169623
[0014] Patent Document 4: Japanese Patent Application Publication No. 2000-302707 Summary of the invention
[0015] Problem that the invention aims to solve
[0016] In order to facilitate molding into PET plastic bottles, chemically recycled polyester is often subjected to high molecular weight polymerization. In addition, the low molecular weight components are reduced during this process. Therefore, the intrinsic viscosity of chemically recycled polyester is often higher than the intrinsic viscosity of polyester for general biaxially oriented polyester film.
[0017] The present inventors have found that, while studying the use of chemically recycled polyester for the production of biaxially oriented polyester films instead of PET plastic bottles, films obtained using chemically recycled polyester are easily broken during stretching, and therefore the film production speed must be excessively reduced.
[0018] Under such circumstances, the present inventors have found that the breakage of the film that may occur during stretching can be suppressed or reduced, and the amount of low molecular weight components that may cause yellow color to be exhibited in the biaxially oriented polyester film can be reduced, thereby completing the present invention.
[0019] The present invention aims to provide a biaxially oriented polyester film which can reduce environmental burden, reduce yellowing, and inhibit or reduce film breakage that may occur during stretching. The present invention also aims to provide a laminate comprising the biaxially oriented polyester film and a packaging container comprising the laminate.
[0020] Solutions for solving problems
[0021] In order to solve this problem, the present invention has the following technical solution [1]. [1]
[0023] A biaxially oriented polyester film comprising chemically recycled polyester,
[0024] In the molecular weight distribution curve obtained by gel permeation chromatography, the area ratio of the region with a molecular weight of 1,000 or less is 1.9% or more and 5.5% or less of the total peak area.
[0025] Here, "chemically recycled polyester" refers to polyester obtained by decomposing polyester contained in used polyester products to a monomer level and polymerizing it again.
[0026] In [1], the biaxially oriented polyester film comprises chemically recycled polyester. Here, “the biaxially oriented polyester film comprises chemically recycled polyester” means that, when the biaxially oriented polyester film comprises a plurality of layers, at least one of the plurality of layers comprises chemically recycled polyester.
[0027] According to [1], since the biaxially oriented polyester film contains chemically recycled polyester, environmental burden can be reduced.
[0028] Furthermore, by setting the area ratio of the region with a molecular weight of 1,000 or less to 5.5% or less, that is, by setting the upper limit of the content of components with a molecular weight of 1,000 or less (hereinafter sometimes referred to as "low molecular weight components"), the yellow color that may be exhibited by the biaxially oriented polyester film can be reduced.
[0029] Furthermore, by setting the area ratio of the region with a molecular weight of 1000 or less to 1.9% or more, that is, by setting a lower limit for the content of the low molecular weight component, it is possible to ensure the content of the low molecular weight component that can function as a plasticizer.
[0030] Furthermore, by making the area ratio of the region with a molecular weight of less than 1000 be 1.9% or more, the molecular weight of the polyester contained in the biaxially oriented polyester film can be limited to a certain level or less. This is explained. Low molecular weight components enter the polyester during the polymerization process, so there is a tendency that the larger the molecular weight of the polyester, the less low molecular weight components there are, and the smaller the molecular weight of the polyester, the more low molecular weight components there are. According to [1], since the area ratio of the region with a molecular weight of less than 1000 is 1.9% or more, in other words, since there is a certain level of low molecular weight components, the molecular weight of the polyester contained in the biaxially oriented polyester film can be limited to a certain level or less.
[0031] Therefore, it is possible to prevent the stress during stretching (in other words, stretching stress) in the production process of the biaxially oriented polyester film from becoming excessively large, and as a result, it is possible to suppress or reduce the film breakage that may occur during stretching.
[0032] The present invention preferably also has the following technical solutions [2] and thereafter. [2]
[0034] The biaxially oriented polyester film according to [1], wherein the color b* value per 1 μm thickness is 0.067 or less.
[0035] According to [2], the yellow color that may be exhibited by the biaxially oriented polyester film can be limited. Therefore, for example, when a printed layer is formed on the biaxially oriented polyester film, the influence of the color tone of the biaxially oriented polyester film on the appearance of the printed layer (in other words, the appearance) can be reduced. In addition, for example, when a packaging container is made using the biaxially oriented polyester film, the influence of the color tone of the biaxially oriented polyester film on the appearance of the content can be reduced. [3]
[0037] The biaxially oriented polyester film according to [1] or [2], wherein the content of the chemically recycled polyester is 20% by mass or more.
[0038] According to [3], the environmental burden can be further reduced. [4]
[0040] A laminate comprising the biaxially oriented polyester film according to any one of [1] to [3] and a sealant layer.
[0041] According to [4], since the laminate includes the sealant layer, a product (eg, a packaging container) including the laminate can be manufactured by heat sealing. [5]
[0043] The laminate according to [4], further comprising a printed layer,
[0044] In at least a portion of the laminate, the printed layer, the biaxially oriented polyester film, and the sealant layer are arranged in this order in the thickness direction of the laminate.
[0045] Here, “the printed layer, the biaxially oriented polyester film, and the sealant layer are arranged in this order in the thickness direction of the laminate” is a statement that allows the presence of other layers between the printed layer and the biaxially oriented polyester film, and between the biaxially oriented polyester film and the sealant layer.
[0046] According to [5], since the laminate includes the printed layer, a design (eg, text, pattern, symbol, etc.) can be added to the laminate or a product including the laminate (eg, a packaging container). [6]
[0048] The laminate according to [4], further comprising a printed layer,
[0049] In at least a portion of the laminate, the biaxially oriented polyester film, the printed layer, and the sealant layer are arranged in this order in the thickness direction of the laminate.
[0050] Here, “the biaxially oriented polyester film, the printed layer, and the sealant layer are arranged in this order in the thickness direction of the laminate” is a statement that allows the presence of other layers between the biaxially oriented polyester film and the printed layer, and between the printed layer and the sealant layer.
[0051] According to [6], since the laminate includes a printed layer, a design (eg, text, pattern, symbol, etc.) can be added to the laminate or a product including the laminate (eg, a packaging container). [7]
[0053] A laminate comprising the biaxially oriented polyester film according to any one of [1] to [3] and an adhesive layer.
[0054] According to [7], since the laminate includes the adhesive layer, a product (for example, a packaging container) including the laminate can be manufactured by pressurization. [8]
[0056] The laminate according to [7], further comprising a printed layer,
[0057] In at least a portion of the laminate, the printed layer, the biaxially oriented polyester film, and the adhesive layer are arranged in this order in the thickness direction of the laminate.
[0058] Here, “the printed layer, the biaxially oriented polyester film, and the adhesive layer are arranged in this order in the thickness direction of the laminate” is a statement that allows the presence of other layers between the printed layer and the biaxially oriented polyester film, and between the biaxially oriented polyester film and the adhesive layer.
[0059] According to [8], since the laminate includes a printed layer, a design (eg, text, pattern, symbol, etc.) can be added to the laminate or a product including the laminate (eg, a packaging container). [9]
[0061] The laminate according to [7], further comprising a printed layer,
[0062] In at least a portion of the laminate, the biaxially oriented polyester film, the printed layer, and the adhesive layer are arranged in this order in the thickness direction of the laminate.
[0063] Here, “the biaxially oriented polyester film, the printed layer, and the adhesive layer are arranged in this order in the thickness direction of the laminate” is a statement that allows the presence of other layers between the biaxially oriented polyester film and the printed layer, and between the printed layer and the adhesive layer.
[0064] According to [9], since the laminate includes a printed layer, a design (eg, text, pattern, symbol, etc.) can be added to the laminate or a product including the laminate (eg, a packaging container).
[10]
[0066] A laminate comprising:
[0067] The biaxially oriented polyester film according to any one of [1] to [3]; and
[0068] At least one support layer selected from the group consisting of polyethylene terephthalate, stretched nylon and polyethylene films.
[11]
[0070] A laminate comprising the biaxially oriented polyester film according to any one of [1] to [3] and a substrate layer.
[12]
[0072] A laminate comprising:
[0073] The biaxially oriented polyester film according to any one of [1] to [3];
[0074] an adhesive layer and / or an anchor coating; and
[0075] Sealing layer.
[13]
[0077] A packaging container comprising the laminate according to any one of [4] to
[12] .
[14]
[0079] The biaxially oriented polyester film described in any one of [1] to [3], the laminate described in any one of [4] to
[12] and / or the packaging container described in
[13] , wherein, in the molecular weight distribution curve of the biaxially oriented polyester film obtained by gel permeation chromatography, the area ratio of the region with a molecular weight of less than 1000 is greater than 1.9% and less than 5.0% of the total peak area.
[15]
[0081] The biaxially oriented polyester film described in any one of [1] to [3], the laminate described in any one of [4] to
[12] and / or the packaging container described in
[13] , wherein, in the molecular weight distribution curve of the biaxially oriented polyester film obtained by gel permeation chromatography, the area ratio of the region with a molecular weight of less than 1000 is greater than 1.9% and less than 4.8% of the total peak area.
[16]
[0083] The biaxially oriented polyester film described in any one of [1] to [3], the laminate described in any one of [4] to
[12] and / or the packaging container described in
[13] , wherein, in the molecular weight distribution curve of the biaxially oriented polyester film obtained by gel permeation chromatography, the area ratio of the region with a molecular weight of less than 1000 is greater than 1.9% and less than 4.6% of the total peak area.
[17]
[0085] The biaxially oriented polyester film described in any one of [1] to [3], the laminate described in any one of [4] to
[12] and / or the packaging container described in
[13] , wherein, in the molecular weight distribution curve of the biaxially oriented polyester film obtained by gel permeation chromatography, the area ratio of the region with a molecular weight of less than 1000 is greater than 1.9% and less than 4.5% of the total peak area.
[18]
[0087] The laminate and / or packaging container according to any one of
[11] to
[17] , wherein the base layer comprises at least one selected from the group consisting of paper, polyethylene terephthalate, stretched nylon, and stretched polypropylene.
[0088] Effects of the Invention
[0089] According to the present invention, there is provided a biaxially oriented polyester film which can reduce environmental burden, can reduce yellowing, and can suppress or reduce film breakage which may occur during stretching. BRIEF DESCRIPTION OF THE DRAWINGS
[0090] Figure 1 This is a schematic cross-sectional view of the biaxially oriented polyester film in this embodiment.
[0091] Figure 2 This is a schematic cross-sectional view of a laminated body in one embodiment.
[0092] Figure 3 This is a schematic cross-sectional view of a laminated body in one embodiment.
[0093] Figure 4A This is a schematic cross-sectional view of a laminated body in one embodiment.
[0094] Figure 4B This is a schematic cross-sectional view of a laminated body in one embodiment.
[0095] Figure 5A This is a schematic cross-sectional view of a laminated body in one embodiment.
[0096] Figure 5B This is a schematic cross-sectional view of a laminated body in one embodiment.
[0097] Fig. 6A This is a schematic cross-sectional view of a laminated body in one embodiment.
[0098] Figure 6B This is a schematic cross-sectional view of a laminated body in one embodiment.
[0099] Figure 7 This is a schematic cross-sectional view of a laminated body in one embodiment.
[0100] Figure 8 This is a schematic cross-sectional view of a laminated body in one embodiment.
[0101] Fig. 9 This is a schematic cross-sectional view of a laminated body in one embodiment.
[0102] Fig.10 This is a schematic cross-sectional view of a laminated body in one embodiment.
[0103] Fig.11 This is a schematic cross-sectional view of a laminated body in one embodiment.
[0104] Fig.12 This is a schematic cross-sectional view of a laminated body in one embodiment.
[0105] Fig.13 This is a schematic cross-sectional view of a laminated body in one embodiment.
[0106] Fig.14 This is a schematic cross-sectional view of a laminated body in one embodiment.
[0107] Fig.15A This is a schematic cross-sectional view of a laminated body in one embodiment.
[0108] Fig. 15B This is a schematic cross-sectional view of a laminated body in one embodiment.
[0109] Fig.16 This is a schematic cross-sectional view of a laminated body in one embodiment.
[0110] Fig.17A This is a schematic cross-sectional view of a laminated body in one embodiment.
[0111] Fig. 17B This is a schematic cross-sectional view of a laminated body in one embodiment. DETAILED DESCRIPTION
[0112] <1. Introduction>
[0113] Hereinafter, embodiments of the present invention will be described.
[0114] In addition, polyethylene terephthalate may be referred to as PET hereinafter. That is, they are used as synonyms.
[0115] Machine Direction (hereinafter referred to as "MD") is sometimes referred to as longitudinal direction. That is, MD and longitudinal direction are used as synonyms.
[0116] Transverse Direction (hereinafter referred to as "TD") is sometimes referred to as width direction. That is, TD and width direction are used as synonyms.
[0117] When describing the embodiment of the present invention, it is sometimes expressed as "the first layer 81, the second layer 82, and the third layer 83 are arranged in sequence in the thickness direction of the biaxially oriented polyester film 8". This expression allows the presence of other layers between the first layer 81 and the second layer 82, and between the second layer 82 and the third layer 83. The same applies to other expressions including the description that a plurality of layers are "arranged in sequence" (in other words, similar expressions).
[0118] <2. Biaxially oriented polyester film>
[0119] like Figure 1 As shown, the biaxially oriented polyester film 8 of the present embodiment is in a film shape.
[0120] The biaxially oriented polyester film 8 contains chemically recycled polyester, and thus, the environmental burden can be reduced.
[0121] Chemically recycled polyester is polyester obtained by decomposing polyester contained in used polyester products to the monomer level and polymerizing it again. Chemically recycled polyester is produced using polyester contained in used polyester products as raw materials, so it can reduce environmental burden. In addition, chemically recycled polyester removes foreign matter (such as catalysts, coloring components, different types of plastics, metals) during the recycling process, so it is superior in terms of hygiene compared to mechanically recycled polyester.
[0122] As the polyester decomposed to the monomer level, there can be used polyester products. The used polyester products can be in the form of bundles, flakes, or pellets. As the used polyester products, used PET plastic bottles are preferred.
[0123] As a method for decomposing polyester to the monomer level, for example, the following method (hereinafter sometimes referred to as "BHET method") can be cited: a bundle of PET plastic bottles is crushed and washed, and at least ethylene glycol (EG) and a catalyst are added to the PET plastic bottle (i.e., flakes) and heated to decompose it to bis(2-hydroxyethyl) terephthalate (BHET) (see Patent Document 3, i.e., Japanese Unexamined Patent Publication No. 2000-169623). As another method for decomposing polyester to the monomer level, for example, the method described in Patent Document 4 (Japanese Unexamined Patent Publication No. 2000-302707) can be cited. Of course, polyester can also be decomposed to the monomer level by methods other than those exemplified here.
[0124] Here, an example of the steps for obtaining BHET by decomposing polyethylene terephthalate constituting a used PET plastic bottle will be described with respect to the BHET method.
[0125] The PET plastic bottle bundle is put into a pulverizer for wet pulverization. In wet pulverization, the PET plastic bottle bundle in washing water (e.g., tap water or groundwater to which detergent is added as needed) can be pulverized. It should be noted that the washing water can be at room temperature or heated.
[0126] The wash water is discharged from the crusher together with the PET bottle flakes and gravity separated to remove foreign matter (e.g. metal, stone, glass, sand).
[0127] Next, the slices are rinsed with ion exchange water and centrifuged for dehydration as necessary.
[0128] After the flakes are melted, a catalyst and an excess of ethylene glycol are added and heated (in other words, depolymerized). Thus, the polyethylene terephthalate constituting the flakes can be depolymerized, and as a result, a depolymerization liquid in which BHET is dissolved in ethylene glycol can be obtained. It should be noted that the flakes are preferably melted in a state containing water (e.g., a state containing water after centrifugal dehydration).
[0129] Remove foreign matter (such as different types of plastics, metals, and glass) floating or precipitated in the depolymerization liquid. It should be noted that the melting point of cyclic oligomers in the depolymerization liquid is higher than that of polyethylene terephthalate, so low molecular weight components such as cyclic oligomers can also be removed by filtration.
[0130] The depolymerization liquid is passed through activated carbon (i.e., liquid passing), and then passed through an ion exchange resin. By passing the depolymerization liquid through activated carbon, coloring components (e.g., pigments, dyes, compounds generated by thermal degradation of organic matter) can be removed. By passing the depolymerization liquid through an ion exchange resin, catalysts (e.g., polymerization catalysts, depolymerization catalysts) and metal ions can be removed.
[0131] Next, the depolymerization liquid is cooled to precipitate BHET, and then BHET and ethylene glycol are separated into solid and liquid forms.
[0132] In order to remove the ethylene glycol remaining in BHET (in other words, to concentrate BHET), vacuum evaporation was performed.
[0133] The concentrated BHET is subjected to molecular distillation.
[0134] According to this procedure, high-purity BHET can be obtained. It should be noted that, although the operation of vacuum evaporation after solid-liquid separation of BHET and ethylene glycol is described here, ethylene glycol may be distilled from the depolymerization liquid instead of this operation.
[0135] As chemically recycled polyesters, for example, chemically recycled polyethylene terephthalate (hereinafter sometimes referred to as "chemically recycled PET"), chemically recycled polybutylene terephthalate, and chemically recycled polyethylene 2,6-naphthalate can be cited. Of course, they may contain copolymer components. Chemically recycled PET is preferred because it is easily available and has excellent mechanical properties and heat resistance. It should be noted that these may be used alone or in combination of two or more.
[0136] Chemically recycled polyester can be copolymerized with other components. Regarding the dicarboxylic acid component as a copolymer component, for example, isophthalic acid, naphthalene dicarboxylic acid, 4,4-diphenyl dicarboxylic acid, adipic acid, sebacic acid, and their ester-forming derivatives can be listed. On the other hand, regarding the diol component as a copolymer component, for example, diethylene glycol, hexamethylene glycol, neopentyl glycol, and cyclohexanedimethanol can be listed. Similarly, polyoxyalkylene glycols such as polyethylene glycol and polypropylene glycol can also be listed. It should be noted that they can be used alone or in combination of two or more. It should be noted that, considering that the PET constituting the PET plastic bottle is usually copolymerized with isophthalic acid in order to improve the moldability of the bottle, the chemically recycled PET preferably contains at least an isophthalic acid component as a copolymer component.
[0137] When the molar number of all dicarboxylic acid components in the chemically recycled polyester is set to 100 mol%, the molar number of the copolymer component is preferably 10 mol% or less, more preferably 8 mol% or less, further preferably 5 mol% or less, and further preferably 3 mol% or less. The molar number of the copolymer component is preferably 0.1 mol% or more, more preferably 1 mol% or more, and further preferably 2 mol% or more. It should be noted that one or more chemically recycled polyesters satisfying such an appropriate molar number of the copolymer component may be included.
[0138] When the chemically recycled polyester is chemically recycled PET, the molar number of the isophthalic acid component is preferably 10 mol% or less, more preferably 8 mol% or less, further preferably 5 mol% or less, and further preferably 3 mol% or less, when the molar number of all dicarboxylic acid components in the chemically recycled PET is set to 100 mol%. The molar number of the isophthalic acid component is preferably 0.1 mol% or more, more preferably 1 mol% or more, and further preferably 2 mol% or more. It should be noted that one or more chemically recycled PETs satisfying such an appropriate molar number of the isophthalic acid component may be contained.
[0139] The intrinsic viscosity of the chemically recycled polyester is preferably 0.50 dl / g or more, more preferably 0.55 dl / g or more, and further preferably 0.57 dl / g or more. If it is 0.50 dl / g or more, the amount of low molecular weight components in the chemically recycled polyester can be limited to a certain extent, so that the yellow color that may appear in the biaxially oriented polyester film 8 can be further reduced. On the other hand, the intrinsic viscosity of the chemically recycled polyester is preferably 0.90 dl / g or less, more preferably 0.85 dl / g or less, further preferably 0.80 dl / g or less, further preferably 0.75 dl / g or less, and further preferably 0.69 dl / g or less. If it is 0.90 dl / g or less, the intrinsic viscosity of the biaxially oriented polyester film 8 can be limited to a certain extent, so that the stress during stretching (in other words, stretching stress) in the manufacturing process of the biaxially oriented polyester film 8 can be further prevented from becoming excessively large, and as a result, the film breakage that may occur during stretching can be further suppressed or reduced. It should be noted that one or two or more chemically recycled polyesters satisfying such an appropriate intrinsic viscosity may be contained.
[0140] In the molecular weight distribution curve of the chemically recycled polyester obtained by gel permeation chromatography (GPC), the area ratio of the region with a molecular weight of 1000 or less may be 3.5% or less, 3.0% or less, 2.5% or less, 2.2% or less, or 2.0% or less of the total peak area. On the other hand, the area ratio may be 0.8% or more, 1.0% or more, or 1.2% or more.
[0141] The melt resistivity of chemically recycled polyester at 285°C may be, for example, 30.0×10 8 Ω·cm or less, can be 25.0×10 8 Ω·cm or less, can be 20.0×10 8 Ω·cm or less, can be 15.0×10 8 Ω·cm or less. The melt resistivity of chemically recycled polyester at 285°C may be, for example, 0.5×10 8Ω·cm or more, can be 1.5×10 8 Ω·cm or more, can be 3.0×10 8 Ω·cm or more, can be 5.0×10 8 Ω·cm or more. It should be noted that the melt resistivity of the chemically recycled polyester is preferably higher than that of the polyester derived from fossil fuels and the mechanically recycled polyester described below. It should be noted that one or more chemically recycled polyesters satisfying such an appropriate melt resistivity may be included.
[0142] Although chemically recycled polyester may contain alkaline earth metal compounds, it is preferred that it contains substantially no alkaline earth metal compounds. Chemically recycled polyester removes catalysts and metal ions during the recycling process, and therefore, by polymerizing using a catalyst other than alkaline earth metal compounds (e.g., a germanium-based catalyst or an antimony-based catalyst), it is possible to completely or substantially contain no alkaline earth metal compounds.
[0143] The content of alkaline earth metal compounds in chemically recycled polyester can be, for example, less than 30 ppm, less than 20 ppm, less than 10 ppm, less than 5 ppm, less than 3 ppm, or 0 ppm, based on alkaline earth metal atoms (i.e., calculated on an alkaline earth metal atom basis).
[0144] Here, the content of the alkaline earth metal compound is the mass of the alkaline earth metal compound based on alkaline earth metal atoms relative to the mass of the chemically recycled polyester (in other words, mass of the alkaline earth metal compound based on alkaline earth metal atoms / mass of the chemically recycled polyester).
[0145] It should be noted that one or more chemically recycled polyesters satisfying such an appropriate alkaline earth metal compound content may be contained.
[0146] The content of magnesium compound in the chemically recycled polyester can be, for example, less than 30 ppm, less than 20 ppm, less than 10 ppm, less than 5 ppm, less than 3 ppm, or 0 ppm, based on magnesium atom basis (i.e., calculated in terms of magnesium atom). It should be noted that one or more chemically recycled polyesters satisfying such an appropriate magnesium compound content can be included.
[0147] The content of phosphorus compounds in the chemically recycled polyester may be 10 ppm or more, 15 ppm or more, 20 ppm or more, or 30 ppm or more, based on phosphorus atoms (i.e., calculated as phosphorus atoms). On the other hand, the content of phosphorus compounds may be 300 ppm or less, 200 ppm or less, or 100 ppm or less, based on phosphorus atoms.
[0148] Here, the content of the phosphorus compound is the mass of the phosphorus compound calculated on a phosphorus atom basis relative to the mass of the chemically recycled polyester (in other words, the mass of the phosphorus compound calculated on a phosphorus atom basis / the mass of the chemically recycled polyester).
[0149] It should be noted that one or more chemically recycled polyesters satisfying such an appropriate phosphorus compound content may be contained.
[0150] When the biaxially oriented polyester film 8 is 100% by mass, the content of the chemically recycled polyester is preferably 10% by mass or more, more preferably 20% by mass or more, and further preferably 30% by mass or more. If it is 10% by mass or more, the environmental burden can be further reduced. On the other hand, when the biaxially oriented polyester film 8 is 100% by mass, the content of the chemically recycled polyester is preferably 95% by mass or less, more preferably 80% by mass or less, and further preferably 70% by mass or less.
[0151] The biaxially oriented polyester film 8 preferably contains polyester derived from fossil fuels, i.e., virgin polyester. The polyester derived from fossil fuels is a polyester obtained by polycondensing a diol compound derived from fossil fuels and a dicarboxylic acid compound derived from fossil fuels. Polyester derived from fossil fuels generally has a wider selection range than chemically recycled polyesters. By using polyester derived from fossil fuels, the adjustable range of the physical properties of the biaxially oriented polyester film 8 can be widened.
[0152] As polyesters derived from fossil fuels, for example, polyethylene terephthalate derived from fossil fuels (hereinafter sometimes referred to as "PET derived from fossil fuels"), polybutylene terephthalate derived from fossil fuels, and polyethylene 2,6-naphthalate derived from fossil fuels can be cited. Of course, they may contain copolymer components. For the reasons of being able to suppress costs and having excellent mechanical properties and heat resistance, PET derived from fossil fuels is preferred, and homopolymer PET derived from fossil fuels is more preferred. It should be noted that homopolymer PET may contain diethylene glycol components that are inevitably contained. It should be noted that they may be used alone or in combination of two or more.
[0153] The intrinsic viscosity of the polyester derived from fossil fuels is preferably 0.50 dl / g or more, more preferably 0.55 dl / g or more, and further preferably 0.57 dl / g or more. If it is 0.50 dl / g or more, the amount of low molecular weight components in the polyester derived from fossil fuels can be limited to a certain extent, so that the yellow color that the biaxially oriented polyester film 8 may present can be further reduced. On the other hand, the intrinsic viscosity of the polyester derived from fossil fuels is preferably 0.75 dl / g or less, more preferably 0.70 dl / g or less, further preferably 0.68 dl / g or less, further preferably 0.66 dl / g or less, and further preferably 0.65 dl / g or less. If it is 0.75 dl / g or less, the stress (in other words, tensile stress) during the stretching process of the biaxially oriented polyester film 8 can be further prevented from becoming excessively large, and as a result, the film breakage that may occur during stretching can be further suppressed or reduced. It should be noted that one or more polyesters derived from fossil fuels that meet such an appropriate intrinsic viscosity can be included.
[0154] In the molecular weight distribution curve of the polyester derived from fossil fuels obtained by gel permeation chromatography (GPC), the area ratio of the region with a molecular weight of 1000 or less may be 3.5% or less, 3.0% or less, or 2.8% or less of the total peak area. On the other hand, the area ratio may be 1.0% or more, 1.5% or more, 1.8% or more, or 2.0% or more.
[0155] The melting resistivity of the polyester derived from fossil fuel at 285°C may be, for example, 2.0×10 8 Ω·cm or less, can be 1.5×10 8 Ω·cm or less, can be 1.0×10 8 Ω·cm or less, can be 0.5×10 8 Ω·cm or less, can be 0.4×10 8 Ω·cm or less. The melting resistivity of polyester derived from fossil fuels at 285°C may be, for example, 0.05×10 8 Ω·cm or more, can be 0.1×10 8 It should be noted that one or two or more polyesters derived from fossil fuels that satisfy such an appropriate melt resistivity may be included.
[0156] The polyester derived from fossil fuel preferably contains an alkaline earth metal compound. The alkaline earth metal compound may be added to the polyester derived from fossil fuel as a polymerization catalyst for producing the polyester derived from fossil fuel, or may be added to reduce the melt resistivity of the biaxially oriented polyester film 8 .
[0157] The content of the alkaline earth metal compound in the polyester derived from fossil fuel is, for example, preferably 30 ppm or more, preferably 35 ppm or more, preferably 40 ppm or more, and preferably 45 ppm or more, based on the alkaline earth metal atom (ie, calculated in terms of alkaline earth metal atoms).
[0158] Here, the content of the alkaline earth metal compound is the mass of the alkaline earth metal compound based on alkaline earth metal atoms relative to the mass of the polyester derived from fossil fuel (in other words, mass of the alkaline earth metal compound based on alkaline earth metal atoms / mass of the polyester derived from fossil fuel).
[0159] It should be noted that one or two or more polyesters derived from fossil fuels may be contained as long as the content of the alkaline earth metal compound satisfies the above-mentioned suitable content.
[0160] The content of the magnesium compound in the polyester derived from fossil fuels is preferably 30 ppm or more, preferably 35 ppm or more, preferably 40 ppm or more, and preferably 45 ppm or more, based on the magnesium atom standard (i.e., calculated in terms of magnesium atoms). It should be noted that one or more polyesters derived from fossil fuels that satisfy such an appropriate magnesium compound content may be included.
[0161] The content of phosphorus compounds in the polyester derived from fossil fuels may be 10 ppm or more, 15 ppm or more, 20 ppm or more, or 30 ppm or more, based on phosphorus atoms (i.e., calculated as phosphorus atoms). On the other hand, the content of phosphorus compounds may be 300 ppm or less, 200 ppm or less, or 100 ppm or less, based on phosphorus atoms.
[0162] Here, the content of the phosphorus compound is the mass of the phosphorus compound based on phosphorus atoms relative to the mass of the polyester derived from fossil fuel (in other words, the mass of the phosphorus compound based on phosphorus atoms / the mass of the polyester derived from fossil fuel).
[0163] It should be noted that one or two or more polyesters derived from fossil fuels may be contained so as to satisfy such an appropriate phosphorus compound content.
[0164] When the biaxially oriented polyester film 8 is 100% by mass, the content of the polyester derived from fossil fuels is preferably 5% by mass or more, more preferably 20% by mass or more, and further preferably 30% by mass or more. If it is 5% by mass or more, the adjustable range of the physical properties of the biaxially oriented polyester film 8 can be further widened. On the other hand, when the biaxially oriented polyester film 8 is 100% by mass, the content of the polyester derived from fossil fuels is preferably 90% by mass or less, more preferably 80% by mass or less, and further preferably 70% by mass or less.
[0165] The biaxially oriented polyester film 8 may or may not contain mechanically recycled polyester. Mechanically recycled polyester refers to polyester obtained from used polyester products without undergoing an operation of decomposing the polyester contained in the used polyester products to a monomer level. Mechanically recycled polyester is obtained by, for example, pulverizing and washing the used polyester products and regenerating them into flakes or pellets as needed.
[0166] In the molecular weight distribution curve of the mechanically recycled polyester obtained by gel permeation chromatography (GPC), the area ratio of the region with a molecular weight of 1000 or less may be 4.5% or less of the total peak area, or 4.0% or less. On the other hand, the area ratio may be 2.5% or more, 3.0% or more, or 3.2% or more.
[0167] The biaxially oriented polyester film 8 preferably contains substantially no mechanically recycled polyester. When the biaxially oriented polyester film 8 is set to 100% by mass, the content of the mechanically recycled polyester is preferably 3% by mass or less, more preferably 1% by mass or less, and further preferably 0.1% by mass or less. The biaxially oriented polyester film 8 preferably contains no mechanically recycled polyester at all.
[0168] The biaxially oriented polyester film 8 may comprise bio-based polyester.
[0169] When the biaxially oriented polyester film 8 is set to 100 mass%, the polyester content (i.e., the polyester content including chemically recycled polyester) is preferably 80 mass% or more, more preferably 90 mass% or more, further preferably 95 mass% or more, and further preferably 98 mass% or more.
[0170] The biaxially oriented polyester film 8 may contain resins other than polyester (eg, chemically recycled polyester, polyester derived from fossil fuels).
[0171] The biaxially oriented polyester film 8 preferably further contains particles. Here, "the biaxially oriented polyester film 8 contains particles" means that, when the biaxially oriented polyester film 8 includes a plurality of layers, at least one layer among the plurality of layers contains particles.
[0172] As particles, for example, inorganic particles and organic particles can be listed. As inorganic particles, for example, silica (silicon oxide) particles, alumina (aluminum oxide) particles, titanium dioxide particles, calcium carbonate particles, kaolin particles, crystalline glass fillers, kaolin particles, talc particles, silica-alumina composite oxide particles, and barium sulfate particles can be listed. Among them, silica particles, calcium carbonate particles, and alumina particles are preferred, and silica particles and calcium carbonate particles are more preferred. For the reason that the haze can be reduced, silica particles are particularly preferred. On the other hand, as organic particles, for example, acrylic resin particles, melamine resin particles, silicone resin particles, and cross-linked polystyrene particles can be listed. Among them, acrylic resin particles are preferred. As acrylic resin particles, for example, particles formed by polymethacrylate, polymethyl acrylate or their derivatives can be listed. It should be noted that they can be used alone or in combination of two or more.
[0173] The weight average particle size of the particles is preferably 0.5 μm or more, more preferably 0.8 μm or more, and further preferably 1.5 μm or more. If it is 0.5 μm or more, it is possible to form bumps and depressions on the surface of the biaxially oriented polyester film 8. Therefore, it is possible to impart slippage to the biaxially oriented polyester film 8. On this basis, the air that may be trapped when the biaxially oriented polyester film 8 is rolled into a roll is easily removed, and the occurrence of poor appearance such as wrinkles and bubbles can be reduced. On the other hand, the weight average particle size of the particles is preferably 4.0 μm or less, more preferably 3.8 μm or less, and further preferably 3.0 μm or less. If it is 4.0 μm or less, it is possible to prevent the biaxially oriented polyester film 8 from having large protrusions.
[0174] The content of particles in the biaxially oriented polyester film 8 is preferably 100 ppm or more. If it is 100 ppm or more, the biaxially oriented polyester film 8 can be further given slipperiness, and the occurrence of poor appearance can be further reduced. On the other hand, the content of particles in the biaxially oriented polyester film 8 is preferably 1000 ppm or less, and more preferably 800 ppm or less. If it is 1000 ppm or less, the arithmetic mean height Sa and the maximum protrusion height Sp on the surface of the biaxially oriented polyester film 8 can be prevented from becoming too high. On this basis, the voids that may be generated in the biaxially oriented polyester film 8 can be reduced, and therefore, the deterioration of transparency caused by the voids can be suppressed.
[0175] Here, the content of particles is the mass of particles relative to the mass of the biaxially oriented polyester film 8 (in other words, the mass of particles / the mass of the biaxially oriented polyester film 8).
[0176] The biaxially oriented polyester film 8 may further contain additives such as an antioxidant, a heat stabilizer, an antistatic agent, an ultraviolet absorber, a plasticizer, and a pigment.
[0177] In the molecular weight distribution curve obtained by gel permeation chromatography (GPC) of the biaxially oriented polyester film 8, the area ratio of the region with a molecular weight of 1000 or less is 5.5% or less of the total peak area. By setting the upper limit of the content of components with a molecular weight of 1,000 or less (i.e., low molecular weight components) to 5.5% or less, the yellow color that may be exhibited by the biaxially oriented polyester film 8 can be reduced.
[0178] By making the area ratio 5.5% or less, even when a sealant layer is formed on the biaxially oriented polyester film 8, the peel strength between the biaxially oriented polyester film 8 and the sealant layer can be improved. This is considered to be because the decrease in peel strength caused by the low molecular weight component that can function as a plastic component can be suppressed.
[0179] The area ratio may be 5.4% or less, 5.3% or less, 5.2% or less, 5.1% or less, or 5.0% or less. The area ratio may be 4.9% or less, 4.8% or less, 4.7% or less, 4.6% or less, or 4.5% or less.
[0180] On this basis, the area ratio of the region with a molecular weight of 1000 or less is 1.9% or more of the total peak area.
[0181] By setting the content to 1.9% or more, that is, by setting the lower limit of the content of the low molecular weight component, it is possible to ensure the content of the low molecular weight component that can function as a plasticizer.
[0182] By making it 1.9% or more, the molecular weight of the polyester contained in the biaxially oriented polyester film 8 can also be limited to a certain level or less. This is explained. Low molecular weight components enter the polyester during the polymerization process, so there is a tendency that the larger the molecular weight of the polyester, the less low molecular weight components there are, and the smaller the molecular weight of the polyester, the more low molecular weight components there are. According to this embodiment, since the area ratio of the region with a molecular weight of 1000 or less is 1.9% or more, in other words, since there is a certain level of low molecular weight components, the molecular weight of the polyester contained in the biaxially oriented polyester film 8 can be limited to a certain level or less.
[0183] Therefore, it is possible to prevent the stress during stretching (in other words, the tensile stress) in the production process of the biaxially oriented polyester film 8 from becoming excessively large, and as a result, it is possible to suppress or reduce the breakage of the film that may occur during stretching.
[0184] The area ratio may be 2.0% or more, 2.2% or more, 2.4% or more, 2.6% or more, 2.8% or more, or 3.0% or more.
[0185] Color b per 1 μm thickness of biaxially oriented polyester film 8 * The value is preferably 0.067 or less, more preferably 0.060 or less, and further preferably 0.050 or less. If it is 0.067 or less, the yellow color that may appear in the biaxially oriented polyester film 8 can be limited. Therefore, for example, when the biaxially oriented polyester film 8 is formed with a printed layer, the influence of the color tone of the biaxially oriented polyester film 8 on the appearance of the printed layer (in other words, the appearance) can be reduced. In addition, for example, when the biaxially oriented polyester film 8 is used to make a packaging container, the influence of the color tone of the biaxially oriented polyester film 8 on the appearance of the content can be reduced.
[0186] The intrinsic viscosity of the biaxially oriented polyester film 8 is preferably 0.50 dl / g or more, more preferably 0.51 dl / g or more. If it is 0.50 dl / g or more, the mechanical properties can be improved, specifically the tensile strength and the puncture strength can be improved. On the other hand, the intrinsic viscosity of the biaxially oriented polyester film 8 is preferably 0.70 dl / g or less, more preferably 0.65 dl / g or less. If it is 0.70 dl / g or less, the stress (in other words, tensile stress) during the stretching in the manufacturing process of the biaxially oriented polyester film 8 can be further prevented from becoming too large, and as a result, the film breakage that may occur during stretching can be further suppressed or reduced.
[0187] The surface crystallinity of at least one surface of the biaxially oriented polyester film 8 is preferably 1.10 or more, more preferably 1.15 or more, further preferably 1.20 or more, and further preferably 1.25 or more.
[0188] The smaller the molecular weight of the polyester is, the faster the crystallization rate is. Therefore, the lower the molecular weight of the polyester contained in the biaxially oriented polyester film 8 is, the higher the surface crystallinity of the biaxially oriented polyester film 8 is.
[0189] If the surface crystallinity is 1.10 or more, not only the molecular weight of the polyester contained in the biaxially oriented polyester film 8 can be further limited to a certain level or less, but also the amount of low molecular weight components that can function as a plasticizer can be further limited to a certain level or more. Therefore, the stress during stretching (in other words, tensile stress) in the manufacturing process of the biaxially oriented polyester film 8 can be further prevented from becoming excessively large, and as a result, the film breakage that may occur during stretching can be further suppressed or reduced.
[0190] Likewise, the surface crystallinity of both surfaces of the biaxially oriented polyester film 8 is preferably 1.10 or more, more preferably 1.15 or more, further preferably 1.20 or more, and further preferably 1.25 or more.
[0191] The surface crystallinity of at least one side of the biaxially oriented polyester film 8 is preferably 1.35 or less, more preferably 1.34 or less, further preferably 1.33 or less, further preferably 1.32 or less, further preferably 1.31 or less, further preferably 1.30 or less, further preferably 1.29 or less, further preferably 1.28 or less. If it is 1.35 or less, the biaxially oriented polyester film 8 can be prevented from becoming too brittle (in other words, the toughness becomes too poor), so that the mechanical properties can be improved, specifically, the tensile strength and the puncture strength can be improved.
[0192] Similarly, the surface crystallinity of both surfaces of the biaxially oriented polyester film 8 is preferably 1.35 or less, more preferably 1.34 or less, further preferably 1.33 or less, further preferably 1.32 or less, further preferably 1.31 or less, further preferably 1.30 or less, further preferably 1.29 or less, further preferably 1.28 or less.
[0193] It should be noted that the surface crystallinity is determined by ATR-IR. That is, it is determined by using a Fourier transform infrared spectrophotometer and obtaining a spectrum using the total reflection attenuation method. The surface crystallinity is determined at 1340 cm -1 The absorption near 1410 cm -1 The intensity ratio of the absorption near 1340 cm -1 Strength / 1410cm -1 Strength. At 1340cm -1 The absorption near 1410 cm is due to the absorption of the angular vibration of CH2 (trans structure) of ethylene glycol. -1 The absorption appearing nearby is absorption that has nothing to do with crystallinity and orientation.
[0194] ATR-IR measurement was performed under the following conditions.
[0195] FT-IR: Bio Rad DIGILAB, FTS-60A / 896
[0196] Single reflection ATR accessories: golden gate MKII (made by SPECAC)
[0197] Internal reflective element: Diamond
[0198] Angle of incidence: 45°
[0199] Resolution: 4cm -1
[0200] Cumulative times: 128 times
[0201] The higher the melting point of the biaxially oriented polyester film 8, the better the heat resistance of the biaxially oriented polyester film 8. In view of this, the melting point of the biaxially oriented polyester film 8 is preferably 251°C or higher, and more preferably 252°C or higher. On the other hand, the melting point of the biaxially oriented polyester film 8 is preferably 270°C or lower, and more preferably 268°C or lower. If it is 270°C or lower, when the raw material polyester (e.g., chemically recycled polyester) used to form the biaxially oriented polyester film 8 is melt-extruded, the viscosity can be prevented from becoming too high, and as a result, high-speed film formation can be performed.
[0202] The melt resistivity of the biaxially oriented polyester film 8 at 285°C is preferably 1.0×10 8 Ω·cm or less, more preferably 0.5×10 8 Ω·cm or less, more preferably 0.25×10 8 Ω·cm or less. If 1.0×10 8 Ω·cm or less, when the melt-extruded film-like polyester composition is made to adhere to the cooling cylinder by the electrostatic bonding casting method during the manufacturing process of the biaxially oriented polyester film 8, the surface of the polyester composition can be effectively charged with static electricity, so that the polyester composition can be well adhered to the cooling cylinder. Therefore, the film-making speed will not be excessively reduced, and the generation of pinner bubbles (i.e., streak-shaped defects caused by the entry of air between the polyester composition and the cooling cylinder) can be suppressed. It should be noted that the film-making speed is the travel speed (m / min) of the biaxially oriented polyester film 8 when the biaxially oriented polyester film 8 is wound into a parent roll. The film-making speed can be calculated by multiplying the casting speed by the MD stretching ratio. On the other hand, the melt resistivity can be, for example, 0.01×10 8 Ω·cm or more, can be 0.03×10 8 Ω·cm or more, can be 0.05×10 8 Ω·cm or more. If 0.01×10 8 If the molten resistivity is less than Ω·cm, the generation of foreign matter (for example, foreign matter caused by alkaline earth metal compounds that can reduce the melt resistivity) can be suppressed or reduced.
[0203] The melt resistivity of the biaxially oriented polyester film 8 can be adjusted by the content of the alkaline earth metal compound and the content of the phosphorus compound in the biaxially oriented polyester film 8. For example, the alkaline earth metal atoms (hereinafter sometimes referred to as "M2") constituting the alkaline earth metal compound have the effect of reducing the melt resistivity. Therefore, the more the content of the alkaline earth metal compound is increased, the lower the melt resistivity can be. On the other hand, it can be considered that the phosphorus compound itself does not have the effect of reducing the melt resistivity of the biaxially oriented polyester film 8, and the presence of the alkaline earth metal compound helps to reduce the melt resistivity. The reason is not clear, but it can be considered that this is because: by containing the phosphorus compound, the generation of foreign matter can be suppressed and the amount of charge carriers can be increased.
[0204] As alkaline earth metal compounds, for example, hydroxides of alkaline earth metals, aliphatic dicarboxylates (acetates, butyrates, etc., preferably acetates), aromatic dicarboxylates, salts formed with compounds having phenolic hydroxyl groups (salts formed with phenol, etc.), etc. can be listed. As alkaline earth metals, for example, magnesium, calcium, strontium, and barium can be listed. Among them, magnesium is preferred. More specifically, magnesium hydroxide, magnesium acetate, calcium acetate, strontium acetate, barium acetate, etc. can be listed. Among them, magnesium acetate is preferred. Alkaline earth metal compounds can be used alone or in combination of two or more. It should be noted that, as a definition of alkaline earth metals, it is generally believed that magnesium is not included in alkaline earth metals, but in this specification, alkaline earth metals are used as a term including magnesium. In other words, in this specification, alkaline earth metals refer to elements of Group IIa of the periodic table.
[0205] It should be noted that chemically recycled polyester removes catalysts and metal ions during the recycling process and therefore does not contain any or substantially no alkaline earth metal compounds. Therefore, the content of alkaline earth metal compounds can be adjusted by combining chemically recycled polyester with other polyesters (e.g., polyester derived from fossil fuels, masterbatch to which alkaline earth metal compounds are added).
[0206] The content of the alkaline earth metal compound in the biaxially oriented polyester film 8 is preferably 20 ppm or more, more preferably 22 ppm or more, and further preferably 24 ppm or more, based on the alkaline earth metal atom standard (i.e., calculated in terms of alkaline earth metal atoms). On the other hand, the content of the alkaline earth metal compound is preferably 400 ppm or less, more preferably 350 ppm or less, and further preferably 300 ppm or less, based on the alkaline earth metal atom standard. If it is 400 ppm or less, the generation of foreign matter and coloring caused by the alkaline earth metal compound can be suppressed.
[0207] Here, the content of the alkaline earth metal compound is the mass of the alkaline earth metal compound based on alkaline earth metal atoms relative to the mass of the biaxially oriented polyester film 8 (in other words, mass of the alkaline earth metal compound based on alkaline earth metal atoms / mass of the biaxially oriented polyester film 8).
[0208] The content of the magnesium compound in the biaxially oriented polyester film 8 is preferably 20 ppm or more, more preferably 22 ppm or more, and further preferably 24 ppm or more, based on the magnesium atom standard (i.e., calculated in terms of magnesium atoms). On the other hand, the content of the magnesium compound is preferably 400 ppm or less, more preferably 350 ppm or less, and further preferably 300 ppm or less, based on the magnesium atom standard.
[0209] Examples of phosphorus compounds include phosphoric acids (phosphoric acid, phosphorous acid, hypophosphorous acid, etc.) and their esters (alkyl esters, aryl esters, etc.), as well as alkylphosphonic acids, arylphosphonic acids, and their esters (alkyl esters, aryl esters, etc.). Preferred phosphorus compounds include phosphoric acid, aliphatic esters of phosphoric acid (alkyl esters of phosphoric acid, etc.; for example, mono-C1-6 alkyl phosphates such as monomethyl phosphate, monoethyl phosphate, monobutyl phosphate; di-C1-6 alkyl phosphates such as dimethyl phosphate, diethyl phosphate, dibutyl phosphate; tri-C1-6 alkyl phosphates such as trimethyl phosphate, triethyl phosphate, tributyl phosphate, etc.), aromatic esters of phosphoric acid (mono-, di- or tri-C6-9 aryl esters of phosphoric acid such as triphenyl phosphate and tricresyl phosphate, etc.), aliphatic esters of phosphorous acid (alkyl esters of phosphorous acid, etc.; for example, phosphorous acid Phosphorus compounds include phosphonic acid (mono- or di-C1-6 alkyl esters of C1-6 alkyl phosphonic acid such as trimethyl phosphonate and tributyl phosphite), alkylphosphonic acid (C1-6 alkyl phosphonic acid such as methylphosphonic acid and ethylphosphonic acid), alkylphosphonic acid alkyl esters (mono- or di-C1-6 alkyl esters of C1-6 alkylphosphonic acid such as dimethyl methylphosphonate and dimethyl ethylphosphonate), arylphosphonic acid alkyl esters (mono- or di-C1-6 alkyl esters of C6-9 arylphosphonic acid such as dimethyl phenylphosphonate and diethyl phenylphosphonate), arylphosphonic acid aryl esters (mono- or di-C6-9 aryl esters of C6-9 arylphosphonic acid such as diphenyl phenylphosphonate). Phosphoric acid and trialkyl phosphates (trimethyl phosphate, etc.) are particularly preferred. These phosphorus compounds can be used alone or in combination of two or more.
[0210] The content of phosphorus compounds in the biaxially oriented polyester film 8 is preferably 10 ppm or more, more preferably 11 ppm or more, and further preferably 12 ppm or more, based on phosphorus atom standards (i.e., calculated in terms of phosphorus atoms). If it is 10 ppm or more, the melt resistivity can be effectively reduced. In addition, the generation of foreign matter can be suppressed. The content of phosphorus compounds can be 20 ppm or more, 40 ppm or more, or 50 ppm or more, based on phosphorus atoms. On the other hand, the content of phosphorus compounds is preferably 600 ppm or less, more preferably 550 ppm or less, and further preferably 500 ppm or less, based on phosphorus atoms. If it is 600 ppm or less, the generation of diethylene glycol can be reduced. The content of phosphorus compounds can be 400 ppm or less, 200 ppm or less, or 100 ppm or less, based on phosphorus atoms.
[0211] Here, the content of the phosphorus compound is the mass of the phosphorus compound based on phosphorus atoms relative to the mass of the biaxially oriented polyester film 8 (in other words, the mass of the phosphorus compound based on phosphorus atoms / the mass of the biaxially oriented polyester film 8).
[0212] In the biaxially oriented polyester film 8, the mass ratio of alkaline earth metal atoms (i.e., M2) to phosphorus atoms (P), i.e., the ratio of the mass of M2 to the mass of P (M2 mass / P mass) is preferably 1.0 or more, more preferably 1.1 or more, further preferably 1.2 or more, further preferably 1.3 or more, further preferably 1.4 or more. If it is 1.0 or more, the melt resistivity of the biaxially oriented polyester film 8 can be effectively reduced. On the other hand, the mass ratio is preferably 5.0 or less, more preferably 4.5 or less, further preferably 4.0 or less. If it is 5.0 or less, the generation and coloring of foreign matter can be suppressed.
[0213] When the molar number of all dicarboxylic acid components in the biaxially oriented polyester film 8 is set to 100 mol%, the molar number of the isophthalic acid component is preferably 0.01 mol% or more, more preferably 0.05 mol% or more, further preferably 0.10 mol% or more, further preferably 0.15 mol% or more, further preferably 0.20 mol% or more, and further preferably 0.40 mol% or more. If it is 0.01 mol% or more, the lamination strength of the biaxially oriented polyester film 8 can be improved. On the other hand, the molar number of the isophthalic acid component is preferably 3.0 mol% or less, more preferably 2.5 mol% or less, further preferably 2.2 mol% or less, and further preferably 2.0 mol% or less. If it is 3.0 mol% or less, it is possible to prevent excessive reduction in crystallinity, and therefore, it is possible to prevent excessive reduction in mechanical properties. In addition, the thickness unevenness of the biaxially oriented polyester film 8 can be reduced, and the thermal shrinkage rate of the biaxially oriented polyester film 8 can also be limited.
[0214] The tensile strength in at least one direction of the biaxially oriented polyester film 8 is preferably 180 MPa or more, more preferably 185 MPa or more, and further preferably 190 MPa or more. If it is 180 MPa or more, the biaxially oriented polyester film 8 can be used to produce a product (such as a packaging container) having excellent strength.
[0215] Similarly, the tensile strength of the biaxially oriented polyester film 8 in the MD (ie, 0° direction), 45° direction, TD (ie, 90° direction), and 135° direction is preferably 180 MPa or more, more preferably 185 MPa or more, and further preferably 190 MPa or more.
[0216] The tensile strength in at least one direction of the biaxially oriented polyester film 8 is preferably 350 MPa or less, more preferably 340 MPa or less, and further preferably 330 MPa or less. If it is 350 MPa or less, it is possible to further prevent the stress (in other words, tensile stress) during the stretching process of the biaxially oriented polyester film 8 from becoming excessively large, and as a result, it is possible to further suppress or reduce the film breakage that may occur during the stretching. The tensile strength may be 320 MPa or less.
[0217] Similarly, the tensile strength of the biaxially oriented polyester film 8 in the MD (i.e., 0° direction), 45° direction, TD (i.e., 90° direction), and 135° direction is preferably 350 MPa or less, more preferably 340 MPa or less, and further preferably 330 MPa or less. The tensile strength may be 320 MPa or less.
[0218] The puncture strength of the biaxially oriented polyester film 8 is preferably 0.50 N / μm or more, more preferably 0.52 N / μm or more, and further preferably 0.55 N / μm or more. If it is 0.50 N / μm or more, the biaxially oriented polyester film 8 can be used to produce products (such as packaging containers) with excellent strength. For example, the biaxially oriented polyester film 8 can be used to produce packaging containers that are not easy to open holes.
[0219] The lamination strength of the biaxially oriented polyester film 8 is preferably 3.0 N / 15 mm or more, more preferably 3.5 N / 15 mm or more, and further preferably 4.0 N / 15 mm or more. If it is 3.0 N / 15 mm or more, when the biaxially oriented polyester film 8 is provided with a sealing layer, a product (e.g., a packaging container) that is not easily peeled off can be produced.
[0220] The heat shrinkage rate in the longitudinal direction, i.e., MD, of the biaxially oriented polyester film 8 is preferably 2.0% or less, and more preferably 1.8% or less. If it is 2.0% or less, the frequency of deformation and wrinkles caused by heat can be reduced when the biaxially oriented polyester film 8 is subjected to secondary processing such as vapor deposition processing and printing processing. The heat shrinkage rate in MD can be, for example, 0.5% or more, or 0.8% or more.
[0221] The heat shrinkage rate in the width direction, i.e., TD, of the biaxially oriented polyester film 8 is preferably from -1.0% to 1.0%, more preferably from -0.8% to 0.8%. If it is from -1.0% to 1.0%, the frequency of deformation and wrinkles caused by heat can be reduced during secondary processing such as vapor deposition processing and printing processing.
[0222] The thickness of the biaxially oriented polyester film 8 is preferably 5 μm or more, more preferably 8 μm or more, and further preferably 9 μm or more. If it is 5 μm or more, the rigidity of the biaxially oriented polyester film 8 is excellent, so the frequency of wrinkles when the biaxially oriented polyester film 8 is rolled up can be reduced. On the other hand, the thickness of the biaxially oriented polyester film 8 is preferably 200 μm or less, more preferably 100 μm or less, further preferably 50 μm or less, and particularly preferably 25 μm or less. The thinner the thickness, the more cost can be suppressed.
[0223] The biaxially oriented polyester film 8 includes a first layer 81 (hereinafter also referred to as a "surface layer 81"), a second layer 82 (hereinafter also referred to as a "center layer 82"), and a third layer 83 (hereinafter also referred to as a "surface layer 83"). The first layer 81, the second layer 82, and the third layer 83 are arranged in sequence in the thickness direction of the biaxially oriented polyester film 8. It should be noted that other layers may exist between the first layer 81 and the second layer 82, and between the second layer 82 and the third layer 83.
[0224] The first layer 81, that is, the surface layer 81, preferably contains chemically recycled polyester. If the first layer 81 contains chemically recycled polyester, the environmental burden can be further reduced.
[0225] The description of the chemically recycled polyester in the first layer 81 overlaps with the above description (i.e., the description of the chemically recycled polyester in the biaxially oriented polyester film 8) and is therefore omitted. Therefore, the description of the chemically recycled polyester in the biaxially oriented polyester film 8 can also be used as the description of the chemically recycled polyester in the first layer 81.
[0226] When the first layer 81 is 100% by mass, the content of the chemically recycled polyester is preferably 10% by mass or more, more preferably 20% by mass or more, and further preferably 30% by mass or more. If it is 10% by mass or more, the environmental burden can be further reduced. On the other hand, when the first layer 81 is 100% by mass, the content of the chemically recycled polyester is preferably 95% by mass or less, more preferably 80% by mass or less, and further preferably 70% by mass or less.
[0227] The first layer 81 preferably contains a polyester derived from fossil fuels. The description of the polyester derived from fossil fuels in the first layer 81 overlaps with the above description (i.e., the description of the polyester derived from fossil fuels in the biaxially oriented polyester film 8) and is therefore omitted. Therefore, the description of the polyester derived from fossil fuels in the biaxially oriented polyester film 8 can also be used as the description of the polyester derived from fossil fuels in the first layer 81.
[0228] When the first layer 81 is 100% by mass, the content of the polyester derived from fossil fuels is preferably 5% by mass or more, more preferably 20% by mass or more, and further preferably 30% by mass or more. If it is 5% by mass or more, the adjustable range of the physical properties of the first layer 81 can be ensured to a certain extent. On the other hand, when the first layer 81 is 100% by mass, the content of the polyester derived from fossil fuels can be set to 100% by mass or less. The content of the polyester derived from fossil fuels is preferably 90% by mass or less, more preferably 80% by mass or less, and further preferably 70% by mass or less.
[0229] The first layer 81 may comprise other polyesters, such as mechanically recycled polyesters, bio-based polyesters.
[0230] When the first layer 81 is taken as 100 mass %, the content of the polyester is preferably 80 mass % or more, more preferably 90 mass % or more, further preferably 95 mass % or more, and further preferably 98 mass % or more.
[0231] The first layer 81 may include a resin other than polyester.
[0232] The first layer 81 preferably further contains particles. If the first layer 81 contains particles, it is possible to form unevenness on the surface of the biaxially oriented polyester film 8. Therefore, it is possible to impart slippage to the biaxially oriented polyester film 8. On this basis, air that may be trapped when the biaxially oriented polyester film 8 is rolled into a roll is easily removed, and the occurrence of poor appearance such as wrinkles and bubbles can be reduced.
[0233] The description of the particles in the first layer 81 overlaps with the above description (ie, the description of the particles in the biaxially oriented polyester film 8) and is therefore omitted. Therefore, the description of the particles in the biaxially oriented polyester film 8 can also be used as the description of the particles in the first layer 81.
[0234] The content of particles in the first layer 81 is preferably 500 ppm or more, more preferably 600 ppm or more, and further preferably 700 ppm or more. If it is 500 ppm or more, the biaxially oriented polyester film 8 can be further provided with slip properties, and the occurrence of poor appearance can be further reduced. On the other hand, the content of particles in the first layer 81 can be 3000 ppm or less, 2000 ppm or less, or 1500 ppm or less.
[0235] Here, the content of particles is the mass of particles relative to the mass of the first layer 81 (in other words, the mass of particles / the mass of the first layer 81 ).
[0236] The thickness of the first layer 81 is preferably 0.1 μm or more, more preferably 0.3 μm or more, and further preferably 0.5 μm or more. The thickness of the first layer 81 is preferably 7 μm or less, more preferably 5 μm or less, and further preferably 3 μm or less.
[0237] The description of the third layer 83, i.e., the surface layer 83, overlaps with the description of the first layer 81 and is therefore omitted. Therefore, the description of the first layer 81 can also be used as the description of the third layer 83. For example, the description of chemically recycled polyester, polyester derived from fossil fuels, particles, thickness, etc. related to the first layer 81 can be used as the description of the third layer 83. Of course, the first layer 81 and the third layer 83 can be independent of each other in terms of composition, physical properties (such as thickness), etc. Therefore, for example, the composition of the first layer 81 and the third layer 83 can be the same or different. The thickness of the two can be the same or different.
[0238] The second layer 82, ie, the core layer 82, preferably contains chemically recycled polyester. If the second layer 82 contains chemically recycled polyester, the environmental burden can be further reduced.
[0239] The description of the chemically recycled polyester in the second layer 82 overlaps with the above description (i.e., the description of the chemically recycled polyester in the biaxially oriented polyester film 8) and is therefore omitted. Therefore, the description of the chemically recycled polyester in the biaxially oriented polyester film 8 can also be used as the description of the chemically recycled polyester in the second layer 82.
[0240] When the second layer 82 is 100% by mass, the content of the chemically recycled polyester is preferably 10% by mass or more, more preferably 20% by mass or more, and further preferably 30% by mass or more. If it is 10% by mass or more, the environmental burden can be further reduced. On the other hand, when the second layer 82 is 100% by mass, the content of the chemically recycled polyester is preferably 95% by mass or less, more preferably 80% by mass or less, and further preferably 70% by mass or less.
[0241] The second layer 82 preferably contains a polyester derived from fossil fuels. The description of the polyester derived from fossil fuels in the second layer 82 overlaps with the above description (i.e., the description of the polyester derived from fossil fuels of the biaxially oriented polyester film 8) and is therefore omitted. Therefore, the description of the polyester derived from fossil fuels in the biaxially oriented polyester film 8 can also be used as the description of the polyester derived from fossil fuels in the second layer 82.
[0242] When the second layer 82 is 100% by mass, the content of the polyester derived from fossil fuels is preferably 5% by mass or more, more preferably 20% by mass or more, and even more preferably 30% by mass or more. If it is 5% by mass or more, the adjustable range of the physical properties of the second layer 82 can be ensured to some extent. On the other hand, when the first layer 81 is 100% by mass, the content of the polyester derived from fossil fuels is preferably 90% by mass or less, more preferably 80% by mass or less, and even more preferably 70% by mass or less.
[0243] The second layer 82 may comprise other polyesters, such as mechanically recycled polyesters, bio-based polyesters.
[0244] When the second layer 82 is taken as 100 mass %, the content of the polyester is preferably 80 mass % or more, more preferably 90 mass % or more, further preferably 95 mass % or more, and further preferably 98 mass % or more.
[0245] The second layer 82 may include a resin other than polyester.
[0246] The second layer 82 may or may not contain particles. The description of the particles in the second layer 82 overlaps with the above description (i.e., the description of the particles in the biaxially oriented polyester film 8), and is therefore omitted. Therefore, the description of the particles in the biaxially oriented polyester film 8 can also be used as the description of the particles in the second layer 82. It should be noted that if the second layer 82 does not contain particles, there will be no pores that may be generated around the particles, and therefore, it is possible to prevent the odor components from escaping from the biaxially oriented polyester film 8. On this basis, it is easy to mix and use the recycled raw materials of the edge parts generated in the film-making process, the recycled raw materials of other film-making processes, etc. in a timely manner, so it is also advantageous in terms of cost.
[0247] The content of particles in the second layer 82 may be 3000 ppm or less, 2000 ppm or less, 1500 ppm or less, 1000 ppm or less, 500 ppm or less, 100 ppm or less, 50 ppm or less, or 0 ppm or less.
[0248] Here, the content of particles is the mass of particles relative to the mass of the second layer 82 (in other words, the mass of particles / the mass of the second layer 82 ).
[0249] The thickness of the second layer 82 is preferably greater than the thickness of the first layer 81 and the thickness of the third layer 83. The thickness of the second layer 82 is preferably 5 μm or more, more preferably 8 μm or more, and further preferably 9 μm or more. If it is 5 μm or more, the rigidity of the biaxially oriented polyester film 8 is excellent, so the frequency of wrinkles when the biaxially oriented polyester film 8 is rolled up can be reduced. On the other hand, the thickness of the biaxially oriented polyester film 8 is preferably 40 μm or less, more preferably 30 μm or less, and further preferably 20 μm or less. The thinner the thickness, the more cost can be suppressed.
[0250] Several additional explanations will be given regarding the composition patterns of the first layer 81 , the second layer 82 , and the third layer 83 .
[0251] As the first composition mode (hereinafter also referred to as "composition mode A"), the following mode can be cited: the first layer 81 contains chemically recycled polyester, the second layer 82 contains chemically recycled polyester, and the third layer 83 contains chemically recycled polyester. According to the composition mode A, the chemically recycled polyester with less impurities constitutes the two surface layers of the biaxially oriented polyester film 8, so that the defects in the biaxially oriented polyester film 8 can be reduced. The description of the first layer 81, the second layer 82, and the third layer 83 in the composition mode A overlaps with the above description (i.e., the description of the first layer 81, the second layer 82, and the third layer 83), and is therefore omitted. Therefore, the above description can also be used as the description of the first layer 81, the second layer 82, and the third layer 83 in the composition mode A. Therefore, the first layer 81 can contain polyester other than chemically recycled polyester, the second layer 82 can contain polyester other than chemically recycled polyester, and the third layer 83 can contain polyester other than chemically recycled polyester.
[0252] As a second composition mode (hereinafter also referred to as "composition mode B"), the following mode can be cited: the first layer 81 contains chemically recycled polyester, and the second layer 82 and the third layer 83 do not contain chemically recycled polyester. According to the composition mode B, the chemically recycled polyester with less impurities will constitute the surface layer of the biaxially oriented polyester film 8, so that the defects in the biaxially oriented polyester film 8 can be reduced. The description of the first layer 81, the second layer 82, and the third layer 83 in the composition mode B overlaps with the above description (that is, the description of the first layer 81, the second layer 82, and the third layer 83), and is therefore omitted. Therefore, the above description can also be used as the description of the first layer 81, the second layer 82, and the third layer 83 in the composition mode B. Therefore, the first layer 81 can contain polyester other than chemically recycled polyester.
[0253] It should be noted that in composition mode B, the second layer 82 and / or the third layer 83 preferably contain mechanically recycled polyester. This can further increase the recycled raw material ratio. In other words, the environmental burden can be further reduced.
[0254] As a third composition mode (hereinafter also referred to as "composition mode C"), the following mode can be cited: the second layer 82 contains chemically recycled polyester, and the first layer 81 and the third layer 83 do not contain chemically recycled polyester. The description of the first layer 81, the second layer 82, and the third layer 83 in the composition mode C overlaps with the above description (i.e., the description of the first layer 81, the second layer 82, and the third layer 83), and is therefore omitted. Therefore, the above description can also be used as the description of the first layer 81, the second layer 82, and the third layer 83 in the composition mode C. Therefore, the second layer 82 may contain polyester other than chemically recycled polyester.
[0255] It should be noted that in composition mode C, the first layer 81 and / or the third layer 83 preferably contain mechanically recycled polyester. This can further increase the recycled raw material ratio. In other words, the environmental burden can be further reduced.
[0256] As a fourth composition mode (hereinafter also referred to as "composition mode D"), the following mode can be cited: the first layer 81 contains chemically recycled polyester, the second layer 82 contains chemically recycled polyester, and the third layer 83 does not contain chemically recycled polyester. According to the composition mode D, the chemically recycled polyester with less impurities constitutes the surface layer of the biaxially oriented polyester film 8, so that the defects in the biaxially oriented polyester film 8 can be reduced. The description of the first layer 81, the second layer 82, and the third layer 83 in the composition mode D overlaps with the above description (i.e., the description of the first layer 81, the second layer 82, and the third layer 83), and is therefore omitted. Therefore, the above description can also be used as the description of the first layer 81, the second layer 82, and the third layer 83 in the composition mode D. Therefore, the first layer 81 can contain polyester other than chemically recycled polyester, and the second layer 82 can contain polyester other than chemically recycled polyester.
[0257] It should be noted that in composition mode D, the third layer 83 preferably contains mechanically recycled polyester. This can further increase the recycled raw material ratio. In other words, the environmental burden can be further reduced.
[0258] As a fifth composition mode (hereinafter also referred to as "composition mode E"), the following mode can be cited: the first layer 81 contains chemically recycled polyester, the second layer 82 does not contain chemically recycled polyester, and the third layer 83 contains chemically recycled polyester. According to the composition mode E, the chemically recycled polyester with less impurities constitutes the two surface layers of the biaxially oriented polyester film 8, so that the defects in the biaxially oriented polyester film 8 can be reduced. The description of the first layer 81, the second layer 82, and the third layer 83 in the composition mode E overlaps with the above description (i.e., the description of the first layer 81, the second layer 82, and the third layer 83), and is therefore omitted. Therefore, the above description can also be used as the description of the first layer 81, the second layer 82, and the third layer 83 in the composition mode E. Therefore, the first layer 81 can contain polyester other than chemically recycled polyester, and the third layer 83 can contain polyester other than chemically recycled polyester.
[0259] It should be noted that in composition mode E, the second layer 82 preferably contains mechanically recycled polyester. This can further increase the recycled raw material ratio. In other words, the environmental burden can be further reduced.
[0260] The biaxially oriented polyester film 8 can be made according to the following steps: the raw materials for forming the first layer 81 are supplied to the first extruder, the raw materials for forming the second layer 82 are supplied to the second extruder, and the raw materials for forming the third layer 83 are supplied to the third extruder, and then they are melted, and then introduced into a T-die from the first extruder, the second extruder and the third extruder, and they are stacked in the T-die, and then they are extruded from the T-die, solidified by a cooling cylinder, and biaxially stretched. Of course, these raw materials can also be introduced into a feed block from the first extruder, the second extruder and the third extruder, and they are stacked by a feed block, and then they are extruded from the T-die. It should be noted that methods other than the T-die method, such as the tubular method, can be used.
[0261] Examples of the raw material for forming the first layer 81 include chemically recycled polyester, polyester derived from fossil fuels, master batches containing particles, and master batches containing alkaline earth metal compounds / phosphorus compounds (hereinafter sometimes referred to as "MP master batches"). It is preferred that at least these be used as the raw material for forming the first layer 81.
[0262] The particle-containing masterbatch may include polyester and particles (eg, silica). Among various raw materials used to form the first layer 81, the particle-containing masterbatch may include particles (eg, silica) at the highest concentration.
[0263] The polyester of the masterbatch containing particles can be chemically recycled polyester, polyester derived from fossil fuels, mechanically recycled polyester, or biomass polyester. Among them, chemically recycled polyester and polyester derived from fossil fuels are preferred, and polyester derived from fossil fuels is more preferred.
[0264] The content of particles in the particle-containing masterbatch is preferably 5000 ppm or more, more preferably 10000 ppm or more, and further preferably 20000 ppm or more. On the other hand, the content of particles in the particle-containing masterbatch may be 1000000 ppm or less, 200000 ppm or less, or 100000 ppm or less.
[0265] Here, the content of particles is the mass of particles relative to the mass of a masterbatch containing the particles (in other words, the mass of particles / the mass of a masterbatch containing the particles).
[0266] On the other hand, the MP masterbatch (i.e., the masterbatch containing alkaline earth metal compound / phosphorus compound) may contain polyester, alkaline earth metal compound and phosphorus compound. Among various raw materials used to form the first layer 81, the MP masterbatch contains alkaline earth metal compound at the highest concentration and contains phosphorus compound at the highest concentration.
[0267] The polyester of the MP masterbatch may be chemically recycled polyester, polyester derived from fossil fuels, mechanically recycled polyester, or biomass polyester. Among them, chemically recycled polyester and polyester derived from fossil fuels are preferred, and polyester derived from fossil fuels is more preferred. It should be noted that the MP masterbatch can be prepared by, for example, adding a large amount of alkaline earth metal compounds and phosphorus compounds when polymerizing polyester.
[0268] The content of the alkaline earth metal compound in the MP masterbatch is preferably 200 ppm or more, preferably 400 ppm or more, preferably 600 ppm or more, and preferably 700 ppm or more, based on the alkaline earth metal atom standard (i.e., calculated in terms of alkaline earth metal atoms). The content of the alkaline earth metal compound is preferably 3000 ppm or less, 2000 ppm or less, and 1500 ppm or less, based on the alkaline earth metal atom standard.
[0269] Here, the content of the alkaline earth metal compound is the mass of the alkaline earth metal compound based on alkaline earth metal atoms relative to the mass of the MP masterbatch (in other words, mass of the alkaline earth metal compound based on alkaline earth metal atoms / mass of the MP masterbatch).
[0270] The content of the magnesium compound in the MP masterbatch is preferably 200 ppm or more, preferably 400 ppm or more, preferably 600 ppm or more, and preferably 700 ppm or more, based on the magnesium compound atom standard (i.e., calculated in terms of magnesium compound atoms). The content of the alkaline earth metal compound is, for example, 3000 ppm or less, 2000 ppm or less, and 1500 ppm or less, based on the magnesium compound atom standard.
[0271] The content of the phosphorus compound in the MP masterbatch is preferably 150 ppm or more, more preferably 300 ppm or more, further preferably 350 ppm or more, and further preferably 400 ppm or more, based on the phosphorus atom standard (i.e., calculated in terms of phosphorus atoms). On the other hand, the content of the phosphorus compound can be 1000 ppm or less, 800 ppm or less, or 700 ppm or less, based on the phosphorus atom standard.
[0272] Here, the content of the phosphorus compound is the mass of the phosphorus compound based on phosphorus atoms relative to the mass of the MP masterbatch (in other words, the mass of the phosphorus compound based on phosphorus atoms / the mass of the MP masterbatch).
[0273] It should be noted that a masterbatch containing an alkaline earth metal compound and a masterbatch containing a phosphorus compound can be used instead of the MP masterbatch. The masterbatch containing an alkaline earth metal compound can include polyester and an alkaline earth metal compound. Among the various raw materials used to form the first layer 81, the masterbatch contains the alkaline earth metal compound at the highest concentration. The masterbatch containing a phosphorus compound can include polyester and a phosphorus compound. Among the various raw materials used to form the first layer 81, the masterbatch contains the phosphorus compound at the highest concentration.
[0274] Examples of the raw material for forming the second layer 82 include chemically recycled polyester, polyester derived from fossil fuels, and master batches containing alkaline earth metal compounds / phosphorus compounds (ie, MP master batches). It is preferred that at least these be used as the raw material for forming the second layer 82 .
[0275] The description of the MP masterbatch in the second layer 82 overlaps with the above description (ie, the description of the MP masterbatch in the first layer 81 ), and is therefore omitted. Therefore, the description of the MP masterbatch in the first layer 81 can also be used as the description of the MP masterbatch in the second layer 82 .
[0276] The description of the raw material for forming the third layer 83 overlaps with the description of the raw material for forming the first layer 81 and is therefore omitted. Thus, the description of the raw material for forming the first layer 81 can also be used as the description of the raw material for forming the third layer 83. Of course, the raw material for forming the first layer 81 and the raw material for forming the third layer 83 can be independent of each other. Thus, for example, these raw materials can be the same or different.
[0277] These raw materials (specifically, raw materials for forming the first layer 81, the second layer 82, and the third layer 83) are preferably dried before being supplied to the extruder. For drying, for example, a dryer such as a hopper dryer, a paddle dryer, or a vacuum dryer can be used.
[0278] The raw materials for forming the first layer 81 are supplied to the first extruder, the raw materials for forming the second layer 82 are supplied to the second extruder, and the raw materials for forming the third layer 83 are supplied to the third extruder, and they are melted, and then introduced into a T die or a feed block from the first extruder, the second extruder, and the third extruder, so that they can be stacked. These raw materials are preferably melted at a temperature above the melting point of the polyester in the raw materials and above 200° C. and below 300° C.
[0279] The polyester composition in a film form can be extruded from the T die and cast onto a cooling drum. In this way, the polyester composition can be rapidly cooled and solidified, and as a result, a substantially non-oriented unstretched film can be obtained. It should be noted that the surface temperature of the cooling drum is preferably 40° C. or less.
[0280] Next, the unstretched film can be subjected to biaxial stretching. By conducting biaxial stretching, mechanical properties such as tensile strength can be improved. Biaxial stretching can be simultaneous biaxial stretching or sequential biaxial stretching. Among them, sequential biaxial stretching is preferred. In sequential biaxial stretching, the unstretched film is preferably stretched along the length direction, i.e., MD, and the sheet after MD stretching is stretched along the width direction, i.e., TD. Thus, a biaxially oriented polyester film 8 having excellent thickness uniformity can be manufactured at a faster film-making speed.
[0281] The temperature when the unstretched film is stretched in the longitudinal direction, i.e., the MD stretching temperature, is preferably 80° C. or higher and 130° C. or lower. The stretching ratio at this time, i.e., the MD stretching ratio, is preferably 3.3 times or higher and 4.7 times or lower. If it is 80° C. or higher and 4.7 times or lower, the shrinkage stress in the longitudinal direction can be reduced, the bending phenomenon can be reduced, and the molecular orientation, thermal shrinkage rate deviation, and strain of the biaxially oriented polyester film 8 in the width direction can be reduced.
[0282] It should be noted that the method of stretching the unstretched film along the longitudinal direction may be, for example, a method of stretching the film in multiple stages between multiple rollers, or a method of stretching the film by heating it with an infrared heater, etc. The latter is preferred because it is easy to increase the temperature and to heat it locally, thereby reducing the damage defects caused by the rollers.
[0283] For at least one side of the film stretched along the length direction, a surface treatment such as corona treatment or plasma treatment can be implemented as needed. For at least one side of the film stretched along the length direction, a resin dispersion or a resin solution can be applied as needed. Thus, functions such as easy slip, easy adhesion, and antistatic properties can be imparted. It should be noted that both surface treatments such as corona treatment or plasma treatment and the application of a resin dispersion or a resin solution can be performed.
[0284] The film stretched in the length direction is introduced into the tentering device, and the two ends of the film are held by clamps. After the film is heated to a specified temperature by hot air, the film is conveyed in the length direction while the distance between the clamps is widened, thereby stretching the film in the width direction.
[0285] The preheating temperature when the film is stretched in the width direction is preferably 100° C. or higher and 130° C. or lower. If it is 100° C. or higher, the shrinkage stress generated when the film is stretched in the longitudinal direction can be reduced, the bending phenomenon can be reduced, and the molecular orientation, thermal shrinkage rate deviation, and strain of the biaxially oriented polyester film 8 in the width direction can be reduced.
[0286] The temperature when the film is stretched in the width direction, i.e., the TD stretching temperature, is preferably 105°C or higher and 135°C or lower. If it is 105°C or higher, the tensile stress in the longitudinal direction generated by TD stretching can be reduced, and the increase of the bending phenomenon can be suppressed. If it is 135°C or lower, even when a polyester with a temperature rise crystallization temperature of about 130°C (such as chemically recycled polyester) is used, it is possible to suppress or reduce the film breakage that may occur during stretching.
[0287] The stretching ratio when the film is stretched along the width direction, i.e., the TD stretching ratio, is preferably 3.5 times or more and 5.0 times or less. If it is 3.5 times or more, it is easy to obtain a high yield in terms of material balance, and it is also possible to suppress the reduction of mechanical strength and the increase of uneven thickness in the width direction. If it is 5.0 times or less, it is possible to suppress or reduce the film breakage that may occur during stretching.
[0288] The biaxially stretched film may be heated to thermally fix it. The thermal fixing temperature is preferably 220°C or higher and 250°C or lower. If it is 220°C or higher, it is possible to prevent the thermal shrinkage in the length direction and the width direction from becoming too high. Therefore, the thermal dimensional stability during secondary processing can be improved. If it is 250°C or lower, it is possible to suppress the increase in the bending phenomenon, and it is possible to reduce the molecular orientation in the width direction of the biaxially oriented polyester film 8, the deviation of the thermal shrinkage, and the strain.
[0289] The heat relaxation treatment may be performed together with the heat setting treatment, or the heat relaxation treatment may be performed separately from the heat setting treatment. The relaxation rate in the width direction during the heat relaxation treatment is preferably 4% or more and 8% or less. If it is 4% or more, it is possible to prevent the heat shrinkage rate in the width direction from becoming too high. Therefore, the thermal dimensional stability during the secondary processing can be improved. If it is 8% or less, it is possible to prevent the tensile stress in the length direction of the central part in the width direction of the film from becoming excessively large, and the increase of the bending phenomenon can be suppressed.
[0290] During the heat relaxation treatment, sometimes, during the period until the biaxially stretched film shrinks due to heat relaxation, the restraining force in the width direction decreases, and the film relaxes due to its own weight, or the film expands due to the accompanying airflow of the hot air blown from the nozzles arranged above and below the film. In this way, the film is in a state where it is easy to move up and down, so the change amount of the orientation angle of the biaxially oriented polyester film 8 is easy to change greatly. In order to keep the film parallel, for example, the wind speed of the hot air blown from the nozzle can be adjusted.
[0291] Corona discharge treatment, glow discharge treatment, flame treatment, surface roughening treatment, etc. may be performed.
[0292] The wide biaxially oriented polyester film 8 stretched and formed according to the above steps can be wound up in a roll form by a winding device. In other words, a mother roll can be produced.
[0293] The width of the mother roll is preferably 5000 mm or more and 10000 mm or less. If it is 5000 mm or more, the cost per unit film area can be suppressed in the subsequent cutting process, vapor deposition processing, printing processing and other secondary processing.
[0294] The roll length of the mother roll is preferably 10000 m or more and 100000 m or less. If it is 10000 m or more, the cost per unit film area can be suppressed in the subsequent cutting process, vapor deposition processing, printing processing and other secondary processing.
[0295] The mother roll can be cut and then wound up to form a roll. In other words, a film roll can be produced.
[0296] The roll width of the film roll is preferably 400 mm or more and 3000 mm or less. If it is 400 mm or more, the frequency of replacing the film roll can be reduced in the printing process, and the cost can be suppressed. If it is 3000 mm or less, the roll width will not be too large, and the roll weight can be prevented from becoming too heavy. In other words, the operability is good.
[0297] The roll length of the film roll is preferably 2000 m or more and 65000 m or less. If it is 2000 m or more, the frequency of replacing the film roll can be reduced in the printing process, and the cost can be suppressed. If it is 65000 m or less, the roller diameter will not be too large, and the roll weight can be prevented from becoming too heavy. In other words, the operability is good.
[0298] The core used in the film roll is not particularly limited, and a cylindrical core made of plastic, metal or paper with a diameter of, for example, 3 inches (37.6 mm), 6 inches (152.2 mm), 8 inches (203.2 mm), etc. can be used.
[0299] The biaxially oriented polyester film 8 can be used for various purposes. For example, it can be suitably used as a packaging container, a label (e.g., a label for a PET plastic bottle), and an outer packaging film for electronic components including the outer packaging of lithium ion batteries. Among them, it can be suitably used for packaging containers. It can be particularly suitably used for food packaging containers.
[0300] <3. Laminated body>
[0301] like Figure 2 As shown, in one embodiment, the laminate 9 includes a biaxially oriented polyester film 8 and a sealant layer 21. Since the laminate 9 includes the sealant layer 21, a product (eg, a packaging container) including the laminate 9 can be manufactured by heat sealing.
[0302] The sealing layer 21 is a layer that can be softened at a lower temperature than the biaxially oriented polyester film 8. That is, the sealing layer 21 can be melted at a lower temperature than the biaxially oriented polyester film 8. The sealing layer 21 can be formed by, for example, a hot melt adhesive, or a film, or by other methods. As materials constituting the sealing layer 21, thermoplastic resins can be listed. As materials constituting the sealing layer 21, polyethylene resins such as high-density polyethylene (HDPE), low-density polyethylene (LDPE), and linear low-density polyethylene (LLDPE); polypropylene resins, ethylene-vinyl acetate copolymers, ethylene-α-olefin random copolymers, and ionomer resins can be listed. It should be noted that the sealing layer 21 can include one of these, or two or more.
[0303] It should be noted that, as polyethylene, biomass polyethylene is preferred from the viewpoint of being able to further reduce environmental burden. Biomass polyethylene is polyethylene produced using biomass ethanol as a raw material. Biomass polyethylene produced using fermented ethanol derived from biomass obtained from plant raw materials as a raw material is particularly preferred. Examples of plant raw materials include corn, sugar cane, beet, and cassava.
[0304] The sealing layer 21 may contain additives. Examples of the additives include oxygen absorbers, plasticizers, ultraviolet stabilizers, antioxidants, anti-coloring agents, matting agents, deodorants, flame retardants, weathering agents, antistatic agents, friction reducing agents, slip agents, mold release agents, antioxidants, ion exchangers, anti-blocking agents, and colorants.
[0305] The thickness of the sealing layer 21 may be, for example, 5 μm or more, or 7 μm or more. The thickness of the sealing layer 21 may be, for example, 50 μm or less, or 30 μm or less. It should be noted that the sealing layer 21 may be a single layer or may be a two or more layer structure.
[0306] like Figure 3 As shown, the laminate 9 may further include a printed layer 11. The laminate 9 may include a printed layer 11, a biaxially oriented polyester film 8, and a sealant layer 21. In at least a portion of the laminate 9, the printed layer 11, the biaxially oriented polyester film 8, and the sealant layer 21 may be arranged in this order in the thickness direction of the laminate 9.
[0307] The printed layer 11 and the ink layer 11 can give a design to the laminate 9. The design can be a pattern such as a pattern, a pattern, a picture, a photo, a figure, or a symbol such as a word, a symbol, or a badge, or can be any combination of two or more of these. The design can be without a pattern.
[0308] The shape of the printed layer 11 when the laminate 9 is viewed along the vertical direction can be appropriately set. When the laminate 9 is viewed along the vertical direction, the size of the printed layer 11 can be the same as the size of the biaxially oriented polyester film 8 or smaller than the biaxially oriented polyester film 8.
[0309] The printed layer 11 may contain a resin. Examples of the resin include acrylic resins, urethane resins, polyester resins, vinyl chloride resins, vinyl acetate copolymer resins, and mixtures of two or more thereof. The printed layer 11 may contain a colorant. Examples of the colorant include pigments and dyes. The printed layer 11 may contain an additive. Examples of the additive include antistatic agents, light blockers, ultraviolet absorbers, plasticizers, lubricants, fillers, stabilizers, lubricants, defoamers, crosslinking agents, anti-blocking agents, antioxidants, and the like.
[0310] The printed layer 11 may be formed of ink. The ink may contain, in addition to the above-mentioned components, a solvent, for example. It should be noted that the ink may be an ink obtained using a raw material derived from biomass.
[0311] The printed layer 11 can be formed by printing ink and drying it. Examples of printing methods include offset printing, gravure printing, and screen printing. Examples of drying methods after printing include hot air drying, hot roll drying, and infrared drying.
[0312] The laminate 9 may further include a paper layer. For example, the laminate 9 may include a paper layer between the biaxially oriented polyester film 8 and the printed layer 11, or may include a paper layer between the printed layer 11 and the sealing layer 21. Among them, it is preferred to include a paper layer between the biaxially oriented polyester film 8 and the printed layer 11. In this case, in at least a portion of the laminate 9, the biaxially oriented polyester film 8, the paper layer, the printed layer 11, and the sealing layer 21 may be arranged in sequence in the thickness direction of the laminate 9 (not shown).
[0313] As the paper layer, for example, high-quality paper, coated paper, coated paper, resin-coated paper, cast-coated paper, paperboard, synthetic paper, impregnated paper, etc. can be used. The thickness of the paper layer is preferably 30 g / m 2 Above and 400g / m 2 the following.
[0314] The paper layer may be laminated to the biaxially oriented polyester film 8 via other layers (eg, adhesive layer, adhesive resin layer, anchor coating layer).
[0315] The adhesive layer can be formed by an adhesive, i.e., a laminating adhesive. For example, it can be formed by applying a laminating adhesive to a biaxially oriented polyester film 8 and / or a paper layer and drying. The laminating adhesive can be a single-liquid curing type or a two-liquid curing type. The laminating adhesive can be a solvent-based type, an aqueous type, or an emulsion type. Examples of the laminating adhesive include vinyl adhesives, (meth) acrylic adhesives, polyamide adhesives, polyester adhesives, polyether adhesives, polyurethane adhesives, epoxy adhesives, and rubber adhesives. It should be noted that they can be used alone or in combination of two or more.
[0316] The thickness of the adhesive layer may be, for example, 0.1 μm or more, or 1 μm or more. The thickness of the adhesive layer may be, for example, 10 μm or less, or 5 μm or less.
[0317] The adhesive resin layer comprises a thermoplastic resin. As the thermoplastic resin, for example, low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, ethylene-acrylic acid copolymer, ethylene-ethyl acrylate copolymer, ethylene-methacrylic acid copolymer, ethylene-methyl methacrylate copolymer, ethylene-maleic acid copolymer, and ionomer resin can be listed. On this basis, resins obtained by graft polymerization and / or copolymerization of at least one of unsaturated carboxylic acid, unsaturated carboxylic acid, unsaturated carboxylic acid anhydride, and ester monomer on polyolefin resin can be listed. Resins obtained by graft modification of maleic anhydride on polyolefin resin can also be listed. It should be noted that they can be used alone or in combination of two or more.
[0318] The thickness of the adhesive resin layer may be, for example, 0.1 μm or more, 1 μm or more, 5 μm or more, or 10 μm or more. The thickness of the adhesive resin layer may be, for example, 100 μm or less, 50 μm or less, 10 μm or less, or 5 μm or less.
[0319] The anchor coating can be formed by a composition comprising a resin and a curing agent. As the resin, for example, urethane, polyester, acrylic, titanium, isocyanate, imine, and polybutadiene resins can be listed. Among them, urethane, polyester, and acrylic resins are preferred. From the viewpoint of close fit, urethane resins are preferred. On the other hand, from the viewpoint of water resistance, acrylic resins are preferred. It should be noted that they can be used alone or in combination of two or more. As the curing agent, for example, epoxy, isocyanate, and melamine curing agents can be listed. It should be noted that they can be used alone or in combination of two or more.
[0320] The composition for forming the anchor coating preferably comprises a silane coupling agent. The silane coupling agent preferably has one or more organic functional groups in the molecule. When the silane coupling agent has multiple (i.e., more than one) organic functional groups in the molecule, the multiple organic functional groups may be the same or different from each other. In other words, the multiple organic functional groups may be independent of each other. As the organic functional group, for example, an alkoxy group, an amino group, an epoxy group, and an isocyanate group may be listed.
[0321] The composition for forming the anchor coating layer may contain a solvent. Examples of the solvent include aromatic solvents such as benzene and toluene; alcohol solvents such as methanol and ethanol; ketone solvents such as acetone and methyl ethyl ketone; ester solvents such as ethyl acetate and butyl acetate; and polyol derivatives such as ethylene glycol monomethyl ether.
[0322] The anchor coating layer can be formed by applying a composition for forming an anchor coating layer to the biaxially oriented polyester film 8 and drying the composition.
[0323] The thickness of the anchor coating layer may be, for example, 0.1 μm or more, or 0.2 μm or more, or 2 μm or less, or 1 μm or less.
[0324] like Figure 4A As shown in the figure, the laminate 9 may further include an inorganic thin film layer 31, that is, a vapor-deposited layer 31. For example, the laminate 9 may include a printed layer 11, a biaxially oriented polyester film 8, an inorganic thin film layer 31, and a sealing layer 21. In at least a portion of the laminate 9, the printed layer 11, the biaxially oriented polyester film 8, the inorganic thin film layer 31, and the sealing layer 21 are arranged in this order in the thickness direction of the laminate 9. Since the laminate 9 includes the inorganic thin film layer 31, the gas barrier property can be improved.
[0325] The inorganic thin film layer 31 may include an inorganic oxide. As inorganic oxides, for example, oxides of silicon (Si), aluminum (Al), magnesium (Mg), calcium (Ca), potassium (K), tin (Sn), sodium (Na), boron (B), titanium (Ti), lead (Pb), zirconium (Zr), and yttrium (Y) can be cited. As a material forming the inorganic thin film layer 31, silicon oxide (i.e., silicon dioxide), aluminum oxide (i.e., alumina), and a mixture of silicon oxide and aluminum oxide are preferred. Among them, for the reason that the softness and compactness of the inorganic thin film layer 31 can be taken into account, a composite oxide of silicon oxide and aluminum oxide is more preferred. In the composite oxide, the mixing ratio of silicon oxide to aluminum oxide is measured by the mass ratio converted by metal atoms, i.e., the mass ratio converted by metal atoms, and Al is preferably 20% by mass or more and 70% by mass or less. If it is 20% by mass or more, the gas barrier properties are excellent. If it is 70% by mass or less, the inorganic thin film layer 31 can be prevented from becoming too hard. It should be noted that the silicon oxide mentioned here refers to various silicon oxides such as SiO and SiO2 or mixtures thereof, and the aluminum oxide refers to various aluminum oxides such as AlO and Al2O3 or mixtures thereof.
[0326] The inorganic thin film layer 31 may be a metal vapor-deposited layer. Examples of metals used in the metal vapor-deposited layer include magnesium, aluminum, titanium, chromium, iron, nickel, copper, zinc, silver, tin, platinum, and gold. Among them, aluminum is preferred. In other words, the inorganic thin film layer 31 is preferably an aluminum vapor-deposited layer.
[0327] The thickness of the inorganic thin film layer 31 may be, for example, greater than 1 nm, greater than 5 nm, greater than 10 nm, or greater than 20 nm. The thickness of the inorganic thin film layer 31 may be, for example, less than 200 nm, less than 100 nm, or less than 50 nm.
[0328] The inorganic thin film layer 31 may be a single layer or may be a two or more layer structure. When the inorganic thin film layer 31 is two or more layers, the composition, physical properties (such as thickness), etc. of these layers may be independent of each other.
[0329] The inorganic thin film layer 31 can be formed by a physical vapor deposition method (PVD method) such as vacuum evaporation, sputtering, and ion plating, a chemical vapor deposition method (CVD method) such as plasma chemical vapor deposition, thermal chemical vapor deposition, and photochemical vapor deposition. It should be noted that when a silicon oxide / aluminum oxide thin film is formed by vacuum evaporation, a mixture of SiO2 and Al2O3, a mixture of SiO2 and Al can be used as an evaporation raw material. These evaporation raw materials are preferably in a granular form. The desired particle size is such that the pressure does not change during evaporation. For example, the particle size is preferably 1 mm to 5 mm. Heating can be performed by resistance heating, high-frequency induction heating, electron beam heating, laser heating, and the like. In addition, reactive evaporation can be performed by introducing oxygen, nitrogen, hydrogen, argon, carbon dioxide, water vapor, etc. as a reaction gas or using ozone addition, ion assistance, and the like. Furthermore, the film forming conditions such as applying a bias voltage to the vapor-deposited body (the laminated thin film for vapor deposition) or heating or cooling the vapor-deposited body can also be changed arbitrarily. Such vapor deposition materials, reaction gases, bias voltage, heating / cooling of the vapor-deposited body, etc. can also be changed in the same manner when sputtering or CVD is used.
[0330] It should be noted that if Figure 4B As shown, the laminate 9 may include a biaxially oriented polyester film 8, an inorganic thin film layer 31, and a sealant layer 21. In at least a portion of the laminate 9, the biaxially oriented polyester film 8, the inorganic thin film layer 31, and the sealant layer 21 may be arranged in this order in the thickness direction of the laminate 9.
[0331] like Figure 5A As shown in the figure, the laminate 9 may further include an anchor coating 32, that is, a covering layer 32. For example, the laminate 9 may include a printed layer 11, a biaxially oriented polyester film 8, an anchor coating 32, an inorganic thin film layer 31, and a sealing layer 21. In at least a portion of the laminate 9, the printed layer 11, the biaxially oriented polyester film 8, the anchor coating 32, the inorganic thin film layer 31, and the sealing layer 21 may be arranged in sequence in the thickness direction of the laminate 9. The anchor coating 32 may connect the biaxially oriented polyester film 8 to the inorganic thin film layer 31.
[0332] The term “anchor coating” including the anchor coating 32 has been described above, but the anchor coating 32 has specific suitable examples, so additional description is given.
[0333] The anchor coating 32 can be formed by a composition comprising a resin and a curing agent. As the resin, for example, urethane, polyester, acrylic, titanium, isocyanate, imine, and polybutadiene resins can be listed. Among them, urethane, polyester, and acrylic resins are preferred. From the viewpoint of close fit, urethane resins are preferred. On the other hand, from the viewpoint of water resistance, acrylic resins are preferred. It should be noted that they can be used alone or in combination of two or more. As the curing agent, for example, epoxy, isocyanate, and melamine curing agents can be listed. It should be noted that they can be used alone or in combination of two or more.
[0334] The composition for forming the anchor coating 32 preferably includes a silane coupling agent. The silane coupling agent preferably has one or more organic functional groups in the molecule. When the silane coupling agent has multiple (i.e., more than one) organic functional groups in the molecule, the multiple organic functional groups may be the same or different from each other. In other words, the multiple organic functional groups may be independent of each other. As the organic functional group, for example, an alkoxy group, an amino group, an epoxy group, and an isocyanate group may be listed.
[0335] The composition for forming the anchor coating 32 preferably contains a resin containing an oxazoline group, in other words, a polymer containing an oxazoline group. The oxazoline group has a high affinity with the inorganic thin film layer 31, and can react with the oxygen-deficient part of the inorganic oxide and the metal hydroxide that may be produced when the inorganic thin film layer 31 is formed, so that it can be firmly adhered to the inorganic thin film layer 31. On this basis, the unreacted oxazoline group present in the anchor coating 32 can react with the carboxylic acid terminal that may be produced in the biaxially oriented polyester film 8 and the anchor coating 32 (for example, the carboxylic acid terminal that can be produced by hydrolysis), so that crosslinking can be formed.
[0336] The composition for forming the anchor coating layer 32 may contain a solvent. Examples of the solvent include aromatic solvents such as benzene and toluene; alcohol solvents such as methanol and ethanol; ketone solvents such as acetone and methyl ethyl ketone; ester solvents such as ethyl acetate and butyl acetate; and polyol derivatives such as ethylene glycol monomethyl ether.
[0337] The anchor coating layer 32 can be formed by applying a composition for forming the anchor coating layer 32 to the biaxially oriented polyester film 8 and drying the composition.
[0338] It should be noted that if Figure 5B As shown, the laminate 9 may include a biaxially oriented polyester film 8, an anchor coating 32, an inorganic thin film layer 31, and a sealing layer 21. In at least a portion of the laminate 9, the biaxially oriented polyester film 8, the anchor coating 32, the inorganic thin film layer 31, and the sealing layer 21 may be arranged in sequence in the thickness direction of the laminate 9.
[0339] like Fig. 6A As shown in FIG. 1 , the laminate 9 may further include a protective layer 33 on the inorganic thin film layer 31. That is, the laminate 9 may further include a protective layer 33 adjacent to the inorganic thin film layer 31. For example, the laminate 9 may include a printed layer 11, a biaxially oriented polyester film 8, an anchor coating 32, an inorganic thin film layer 31, a protective layer 33, and a sealing layer 21. In at least a portion of the laminate 9, the printed layer 11, the biaxially oriented polyester film 8, the anchor coating 32, the inorganic thin film layer 31, the protective layer 33, and the sealing layer 21 may be arranged in sequence in the thickness direction of the laminate 9. The laminate 9 can suppress or reduce the permeation of gas by including the protective layer 33. The protective layer 33 plays a role in improving the gas barrier properties of the laminate 9.
[0340] By forming the protective layer 33 from a composition containing a resin and a curing agent, the gas barrier properties of the laminate 9 can be improved. This is explained. Generally, minute defective portions are dispersed in the inorganic thin film layer 31. By applying such a composition on the inorganic thin film layer 31 to form the protective layer 33, the composition can be allowed to penetrate into the defective portions of the inorganic thin film layer 31, and as a result, the gas barrier properties of the laminate 9 can be improved.
[0341] As resins, for example, urethane resins, polyester resins, acrylic resins, titanium resins, isocyanate resins, imide resins, and polybutadiene resins can be cited. It should be noted that these can be used alone or in combination of two or more. As curing agents, for example, epoxy resins, isocyanate resins, and melamine curing agents can be cited. It should be noted that these can be used alone or in combination of two or more.
[0342] Among them, urethane resins are preferred. Since the polar groups of the urethane bonds of the urethane resin interact with the inorganic thin film layer 31 and the amorphous part of the urethane resin exhibits flexibility, damage to the inorganic thin film layer 31 can be suppressed when a bending load is applied.
[0343] The acid value of the urethane resin is preferably in the range of 10 mgKOH / g to 60 mgKOH / g. It is more preferably in the range of 15 mgKOH / g to 55 mgKOH / g, and further preferably in the range of 20 mgKOH / g to 50 mgKOH / g. If the acid value of the urethane resin is in the above range, when it is made into an aqueous dispersion, the liquid stability is improved, and the protective layer 33 can be uniformly deposited on the highly polar inorganic thin film, so that the coating appearance becomes good.
[0344] The glass transition temperature (Tg) of the urethane resin is preferably 80° C. or higher, more preferably 90° C. or higher. By setting Tg to 80° C. or higher, swelling of the protective layer 33 due to molecular motion during the wet heat treatment process (heating, holding, and cooling) can be reduced.
[0345] From the aspect of improving gas barrier properties, the carbamate resin preferably contains an aromatic or aromatic aliphatic diisocyanate component as a main constituent. Among them, it is particularly preferred to contain a meta-xylylene diisocyanate component. By using such a carbamate resin, the stacking effect of aromatic rings can be utilized to further improve the aggregation force of the carbamate bond, and as a result, good gas barrier properties can be obtained.
[0346] In the polyisocyanate component 100 mol%, the ratio of the aromatic or aromatic aliphatic diisocyanate in the carbamate resin is preferably set to a range of 50 mol% or more (i.e., 50 mol% or more and 100 mol% or less). The ratio of the total amount of the aromatic or aromatic aliphatic diisocyanate is preferably 60 mol% or more and 100 mol% or less, more preferably 70 mol% or more and 100 mol% or less, and further preferably 80 mol% or more and 100 mol% or less. As this resin, the "TAKELAC (registered trademark) WPB" series sold by Mitsui Chemicals, Inc. can be suitably used. If the ratio of the total amount of the aromatic or aromatic aliphatic diisocyanate is 50 mol% or more, good gas barrier properties can be obtained.
[0347] From the viewpoint of improving the affinity with the inorganic thin film layer 31, the carbamate resin preferably has a carboxylic acid group (carboxyl group). In order to introduce a carboxylic acid (salt) group into the carbamate resin, for example, as a polyol component, a polyol compound having a carboxylic acid group such as dimethylol propionic acid and dimethylol butyric acid can be introduced as a copolymer component. In addition, after synthesizing the carbamate resin containing a carboxylic acid group, if it is neutralized with a salt forming agent, a carbamate resin in a water dispersion can be obtained. As salt forming agents, for example, trialkylamines such as ammonia, trimethylamine, triethylamine, triisopropylamine, tri-n-propylamine, and tri-n-butylamine; N-alkylmorpholines such as N-methylmorpholine and N-ethylmorpholine; N-dialkylalkanolamines such as N-dimethylethanolamine and N-diethylethanolamine. They can be used alone or in combination of two or more.
[0348] The composition for forming the protective layer 33 may contain a solvent. Examples of the solvent include aromatic solvents such as benzene and toluene; alcohol solvents such as methanol and ethanol; ketone solvents such as acetone and methyl ethyl ketone; ester solvents such as ethyl acetate and butyl acetate; and polyol derivatives such as ethylene glycol monomethyl ether.
[0349] On the other hand, the protective layer 33 can be formed from a composition that is polycondensed by a sol-gel method. In this way, a protective layer 33 with high gas barrier properties can be formed, thereby improving the gas barrier properties of the laminate 9. Such a composition may contain an alkoxide represented by Formula 1 and contain at least one of a polyvinyl alcohol-based resin and an ethylene-vinyl alcohol copolymer.
[0350] Formula 1R 1 n M(OR 2 ) m
[0351] R 1 represents an organic group having 1 to 8 carbon atoms. 2 represents an organic group having 1 to 8 carbon atoms. M represents a metal atom. n represents an integer greater than 0. m represents an integer greater than 1. n+m represents the atomic valence of M.
[0352] It should be noted that there are multiple R in Formula 1. 1 When multiple R 1 In formula 1, there are multiple R 2 When multiple R 2 Can be independent.
[0353] As the alkoxide represented by Formula 1, at least one of a partial hydrolyzate of the alkoxide and a hydrolysis condensate of the alkoxide can be used. In the partial hydrolyzate of the alkoxide, it is not necessary to hydrolyze all the alkoxy groups. As the hydrolysis condensate of the alkoxide, a dimer or more of the partially hydrolyzed alkoxide can be used, specifically, dimers to hexamers can be used.
[0354] Examples of the metal atom represented by M include silicon, zirconium, titanium, and aluminum. Among them, silicon and titanium are preferred. It should be noted that alkoxides of different metal atoms may be used alone or in combination of two or more.
[0355] As R 1 Examples of the organic group having 1 to 8 carbon atoms include alkyl groups such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-hexyl and n-octyl.
[0356] As R 2 Examples of the organic group include alkyl groups such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-hexyl and n-octyl.
[0357] The composition may include a silane coupling agent. As the silane coupling agent, an organic alkoxysilane containing an organic reactive group may be cited. An organic alkoxysilane having an epoxy group is particularly preferred. As the organic alkoxysilane having an epoxy group, for example, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane may be cited. It should be noted that they may be used alone or in combination of two or more.
[0358] It should be noted that the composition may further include, for example, a sol-gel catalyst, an acid, water and an organic solvent.
[0359] It should be noted that if Figure 6B As shown, the laminate 9 may include a biaxially oriented polyester film 8, an anchor coating 32, an inorganic thin film layer 31, a protective layer 33, and a sealing layer 21. In at least a portion of the laminate 9, the biaxially oriented polyester film 8, the anchor coating 32, the inorganic thin film layer 31, the protective layer 33, and the sealing layer 21 may be arranged in sequence in the thickness direction of the laminate 9.
[0360] like Figure 7 As shown in FIG. 1 , the laminate 9 may further include a sealing layer 22. For example, the laminate 9 may include a sealing layer 22, a biaxially oriented polyester film 8, and a sealing layer 21. In at least a portion of the laminate 9, the sealing layer 22, the biaxially oriented polyester film 8, and the sealing layer 21 may be arranged in sequence in the thickness direction of the laminate 9. Of course, Figure 3 to Figure 6B The laminated body 9 of the stacked structure shown may further include a sealing layer 22. Preferably, of the two sides of the laminated body 9, one side is composed of the sealing layer 21, and the other side is composed of the sealing layer 22. In other words, it is preferred that, of the pair of outermost layers of the laminated body 9, one outermost layer is the sealing layer 21, and the other outermost layer is the sealing layer 22. The description of the sealing layer 22 overlaps with the description of the sealing layer 21, and is therefore omitted. Therefore, the description of the sealing layer 21 can also be used as the description of the sealing layer 22.
[0361] exist Figure 3 , Figure 4A , Figure 5A , Fig. 6A In the description, the printed layer 11, the biaxially oriented polyester film 8, and the sealant layer 21 are arranged in this order in the thickness direction of the laminate 9. Of course, they may not be arranged in this order.
[0362] For example, Figure 8 As shown, in at least a portion of the laminate 9, the biaxially oriented polyester film 8, the printed layer 11, and the sealant layer 21 may be arranged in this order in the thickness direction of the laminate 9. The laminate 9 may include the biaxially oriented polyester film 8, the printed layer 11, and the sealant layer 21.
[0363] like Fig. 9 As shown, in at least a portion of the laminate 9, the biaxially oriented polyester film 8, the printed layer 11, the inorganic thin film layer 31, and the sealing layer 21 may be arranged in sequence in the thickness direction of the laminate 9. The laminate 9 may include the biaxially oriented polyester film 8, the printed layer 11, the inorganic thin film layer 31, and the sealing layer 21.
[0364] like Fig.10 As shown, in at least a portion of the laminate 9, the biaxially oriented polyester film 8, the printed layer 11, the anchor coating layer 32, the inorganic thin film layer 31, and the sealing layer 21 may be arranged in sequence in the thickness direction of the laminate 9. The laminate 9 may include the biaxially oriented polyester film 8, the printed layer 11, the anchor coating layer 32, the inorganic thin film layer 31, and the sealing layer 21.
[0365] like Fig.11 As shown, in at least a portion of the laminate 9, the biaxially oriented polyester film 8, the printed layer 11, the anchor coating layer 32, the inorganic thin film layer 31, the protective layer 33, and the sealing layer 21 may be arranged in sequence in the thickness direction of the laminate 9. The laminate 9 may include the biaxially oriented polyester film 8, the printed layer 11, the anchor coating layer 32, the inorganic thin film layer 31, the protective layer 33, and the sealing layer 21.
[0366] like Fig.12 As shown in FIG. 1 , the laminate 9 may further include a sealing layer 22. For example, the laminate 9 may include a sealing layer 22, a biaxially oriented polyester film 8, a printing layer 11, and a sealing layer 21. In at least a portion of the laminate 9, the sealing layer 22, the biaxially oriented polyester film 8, the printing layer 11, and the sealing layer 21 may be arranged in sequence in the thickness direction of the laminate 9. Of course, Figures 9 to 11 The laminated body 9 of the stacked structure shown may further include a sealing layer 22. Preferably, one of the two sides of the laminated body 9 is composed of the sealing layer 21, and the other side is composed of the sealing layer 22. In other words, it is preferred that one of the pair of outermost layers of the laminated body 9 is the sealing layer 21, and the other outermost layer is the sealing layer 22.
[0367] In the laminate 9, the role played by the biaxially oriented polyester film 8 is not particularly limited. For example, the biaxially oriented polyester film 8 may play the role of maintaining the above-mentioned layers (e.g., the sealing layer 21, the printing layer 11, the inorganic film layer 31), in other words, may play the role of a substrate. On the other hand, the biaxially oriented polyester film 8 may not be used as a substrate, but may be used for the purpose of improving certain physical properties of the laminate 9, such as strength. In other words, the biaxially oriented polyester film 8 used for this purpose plays the role of a support. In other words, the biaxially oriented polyester film 8 may play the role of a support.
[0368] It should be noted that when the biaxially oriented polyester film 8 serves as a support, other layers (eg, resin films, paper layers) may serve as substrates.
[0369] It should be noted that when the biaxially oriented polyester film 8 plays the role of a substrate, the laminate 9 may further include a layer that plays the role of a support (hereinafter referred to as a "support layer"). On the other hand, when the biaxially oriented polyester film 8 plays the role of a support (in other words, when it is a support layer), the laminate 9 may further include a layer that plays the role of a substrate (hereinafter referred to as a "substrate layer").
[0370] exist Figure 2 to Figure 12 In the previous description, the laminate 9 was described with a focus on the biaxially oriented polyester film 8, but from now on, the laminate 9 will be described with a focus on the base material layer and the support layer rather than the biaxially oriented polyester film 8. In other words, the laminate 9 will be described with a different cut-in point. Therefore, the description from now on may overlap with the description so far.
[0371] like Fig.13 As shown, the laminate 9 includes a base material layer 51 and a sealant layer 21. Since the laminate 9 includes the sealant layer 21, a product (for example, a packaging container) including the laminate 9 can be manufactured by heat sealing.
[0372] As the base layer 51, a biaxially oriented polyester film 8 is used. That is, the base layer 51 is a biaxially oriented polyester film 8. On the other hand, the base layer 51 may be a single-layer structure or a structure of two or more layers. For example, the base layer 51 may be a laminated structure of a biaxially oriented polyester film 8 and a resin film (e.g., a biaxially stretched nylon film).
[0373] like Fig.14 As shown, the laminate 9 may further include a printed layer 11. The laminate 9 may include a printed layer 11, a base layer 51, and a sealing layer 21. In at least a portion of the laminate 9, the printed layer 11, the base layer 51, and the sealing layer 21 may be arranged in this order in the thickness direction of the laminate 9.
[0374] like Fig.15A As shown, the laminate 9 may further include an intermediate layer 61. For example, the laminate 9 may include a printed layer 11, a base layer 51, an intermediate layer 61, and a sealing layer 21. In at least a portion of the laminate 9, the printed layer 11, the base layer 51, the intermediate layer 61, and the sealing layer 21 may be arranged in sequence in the thickness direction of the laminate 9.
[0375] The intermediate layer 61 may include a support layer, a gas barrier layer, a metal foil, or two or more of these. Of course, it may include other layers, such as an adhesive layer, an adhesive resin layer, an anchor coating, etc. The intermediate layer 61 may include a printed layer 11. By making the intermediate layer 61 include a support, certain physical properties of the laminate 9, such as strength, can be improved. By making the intermediate layer 61 include a gas barrier layer and a metal foil, the gas barrier properties of the laminate 9 can be improved.
[0376] As the support layer, for example, a resin film and a paper layer can be listed. As the resin film, for example, films containing one or more of resin materials such as polyester, (meth) acrylic resin, polyolefin (such as polyethylene, polypropylene, polymethylpentene), vinyl resin, cellulose resin, ionomer resin, polyamide (nylon 6, nylon 6,6, poly(m-xylylene adipamide (MXD6)) can be listed. Among them, polyester is preferred. In other words, the resin film preferably contains polyester. The resin film can be a stretched resin film or an unstretched resin film. As a stretched resin film, it can be a uniaxially stretched resin film or a biaxially stretched resin film. Among them, from the reason of excellent dimensional stability, a biaxially stretched resin film is preferred.
[0377] The support layer may contain additives. Examples of the additives include oxygen absorbers, plasticizers, ultraviolet stabilizers, antioxidants, anti-coloring agents, matting agents, deodorants, flame retardants, weathering agents, antistatic agents, friction reducers, slip agents, release agents, antioxidants, ion exchangers, anti-blocking agents, and colorants.
[0378] As the support layer, a biaxially oriented polyester film 8 can be used. That is, the support layer can be a biaxially oriented polyester film 8.
[0379] When the biaxially oriented polyester film 8 is used as the support layer, the biaxially oriented polyester film 8, a resin film, or a paper layer may be used as the base layer 51. In this way, when the biaxially oriented polyester film 8 is used as the support layer, the biaxially oriented polyester film 8 may not be used as the base layer 51.
[0380] When a biaxially oriented polyester film 8 is used as the support layer, as the base material layer 51, for example, a biaxially oriented polyester film 8, a resin film other than the biaxially oriented polyester film 8, and a paper layer can be listed. As the resin film, for example, films containing one or more resin materials such as polyester, (meth) acrylic resin, polyolefin (such as polyethylene, polypropylene, polymethylpentene), vinyl resin, cellulose resin, ionomer resin, polyamide (nylon 6, nylon 6,6, poly(m-xylylene adipamide (MXD6)) can be listed. Among them, polyester is preferred. In other words, the resin film preferably contains polyester. The resin film may be a stretched resin film or an unstretched resin film. As a stretched resin film, it may be a uniaxially stretched resin film or a biaxially stretched resin film. Among them, a biaxially stretched resin film is preferred because of its excellent dimensional stability.
[0381] It should be noted that the intermediate layer 61 may include an anchor coating layer 32 on at least one side of the support layer, or may include an inorganic thin film layer 31. The intermediate layer 61 may include a protective layer 33 (not shown).
[0382] The gas barrier layer contains a gas barrier resin. Examples of the gas barrier resin include ethylene-vinyl alcohol copolymer (EVOH), polyvinyl alcohol, polyacrylonitrile, polyamide (e.g., nylon 6, nylon 6,6, poly(m-xylylene adipamide) (MXD6)), polyester, polyurethane, and (meth) acrylic resin. The gas barrier layer may contain two or more gas barrier resins. The gas barrier layer may further contain other resins and may further contain additives.
[0383] The thickness of the gas barrier layer may be, for example, 3 μm or more, 5 μm or more, or 7 μm or more. The thickness of the gas barrier layer may be, for example, 30 μm or less, or 20 μm or less.
[0384] As metal foil, for example, aluminum foil and magnesium foil can be cited. Among them, aluminum foil is preferred. Among them, from the viewpoint of pinhole resistance and ductility, aluminum foil containing iron is preferred. In 100% by mass of aluminum foil, the content of iron is preferably 0.1% by mass or more, and more preferably 0.5% by mass or more. On the other hand, the content of iron is preferably 9.0% by mass or less, and more preferably 2.0% by mass or more.
[0385] The metal foil may be subjected to a pretreatment, and examples of the pretreatment include degreasing, acid cleaning, and alkali cleaning.
[0386] The thickness of the metal foil may be, for example, 3 μm or more, or 6 μm or more. The thickness of the metal foil may be, for example, 100 μm or less, or 25 μm or less.
[0387] Here, a configuration is described in which, in at least a portion of the stack 9, the printed layer 11, the base material layer 51, the intermediate layer 61, and the sealing layer 21 are arranged in sequence in the thickness direction of the stack 9. However, the printed layer 11, the intermediate layer 61, the base material layer 51, and the sealing layer 21 may also be arranged in sequence in the thickness direction of the stack 9 (not shown).
[0388] It should be noted that if Fig. 15B As shown, the laminate 9 may include a base layer 51, an intermediate layer 61, and a sealing layer 21. In at least a portion of the laminate 9, the base layer 51, the intermediate layer 61, and the sealing layer 21 may be arranged in this order in the thickness direction of the laminate 9.
[0389] exist Fig.14 , Fig.15A In the description, the printed layer 11, the base material layer 51, and the sealing layer 21 are arranged in this order in the thickness direction of the laminate 9. However, they may not be arranged in this order.
[0390] For example, Fig.16 As shown, in at least a portion of the laminate 9, the base layer 51, the printed layer 11, and the sealant layer 21 may be arranged in this order in the thickness direction of the laminate 9. The laminate 9 may include the base layer 51, the printed layer 11, and the sealant layer 21.
[0391] like Fig.17A As shown, in at least a portion of the laminate 9, the base layer 51, the printed layer 11, the intermediate layer 61, and the sealing layer 21 may be arranged in this order in the thickness direction of the laminate 9. The laminate 9 may include the base layer 51, the printed layer 11, the intermediate layer 61, and the sealing layer 21.
[0392] like Fig. 17B As shown, in at least a portion of the laminate 9, the base layer 51, the intermediate layer 61, and the sealant layer 21 may be arranged in this order in the thickness direction of the laminate 9. The laminate 9 may include the base layer 51, the intermediate layer 61, and the sealant layer 21.
[0393] have Figure 13 to Figure 17B The stacked body 9 shown in the stacked structure may further include a sealing layer 22 (not shown). Preferably, one of the two sides of the stacked body 9 is composed of the sealing layer 21, and the other side is composed of the sealing layer 22. In other words, preferably, one of the pair of outermost layers of the stacked body 9 is the sealing layer 21, and the other outermost layer is the sealing layer 22.
[0394] So far, the structure of the laminate 9 including the sealing layer 21 and the sealing layer 22 as required has been described, but of course, it is not limited to this. The laminate 9 may include an adhesive layer instead of at least one of the sealing layer 21 and the sealing layer 22. The adhesive layer may be formed by an adhesive. As adhesives, for example, synthetic rubbers such as styrene-butadiene rubber, acrylonitrile-butadiene rubber, and polyisobutylene rubber; natural rubber, acrylic resin, silicone resin, and polypropylene can be listed. It should be noted that they can be used alone or in combination of two or more.
[0395] As described above, the laminate 9 may have the following structure:
[0396] comprising a substrate layer 51 and a sealing layer 21 or an adhesive layer,
[0397] The substrate layer 51 includes a biaxially oriented polyester film 8 .
[0398] On the other hand, the laminate 9 may also be configured as follows:
[0399] The invention comprises a base material layer 51 and an intermediate layer 61 and comprises a sealing layer 21 or an adhesive layer,
[0400] The intermediate layer 61 comprises a biaxially oriented polyester film 8 .
[0401] Above, refer to Figure 2 to Figure 17B , the laminate 9 has been described. From this point on, more specific examples will be given.
[0402] Prior to this, the meanings of the abbreviations are shown below.
[0403] CRF biaxially oriented polyester film 8
[0404] PET Polyethylene terephthalate
[0405] ONY Stretch Nylon
[0406] OPP Oriented Polypropylene
[0407] CPP Unstretched Polypropylene
[0408] PVC Polyvinyl chloride
[0409] PE Polyethylene
[0410] PEF Polyethylene Film
[0411] Al
[0412] MO metal oxide
[0413] MOR Metal Alkoxide
[0414] In the example given here, the base material layer 51 is a biaxially oriented polyester film 8 .
[0415] (1) Base material layer (CRF) / adhesive layer / heat seal layer (PEF)
[0416] (2) Base material layer (CRF) / heat sealing layer (PE)
[0417] (3) Base material layer (CRF) / anchor coating / heat sealing layer (PE)
[0418] (4) Base material layer (CRF) / anchor coating / adhesive resin layer (PE) / heat sealing layer (PEF)
[0419] (5) Base material layer (CRF) / adhesive layer
[0420] (6) Base material layer (CRF) / inorganic film layer (MO) / protective layer (MOR) / adhesive layer / heat sealing layer (PEF)
[0421] (7) Base material layer (CRF) / inorganic film layer (MO) / protective layer (MOR) / heat sealing layer (PE)
[0422] (8) Base material layer (CRF) / inorganic film layer (MO) / protective layer (MOR) / anchor coating / heat sealing layer (PE)
[0423] (9) Base material layer (CRF) / inorganic film layer (MO) / protective layer (MOR) / anchor coating / adhesive resin layer (PE) / heat seal layer (PEF)
[0424] (10) Base material layer (CRF) / inorganic thin film layer (Al) / adhesive layer
[0425] (11) Base material layer (CRF) / inorganic film layer (Al) / heat sealing layer (PE)
[0426] (12) Base material layer (CRF) / inorganic film layer (Al) / anchor coating / heat sealing layer (PE)
[0427] In the examples given here, the base material layer 51 is also a biaxially oriented polyester film 8 .
[0428] (1) Base material layer (CRF) / Printing layer / Adhesive layer / Heat seal layer (PEF)
[0429] (2) Base material layer (CRF) / printing layer / heat sealing layer (PE)
[0430] (3) Base material layer (CRF) / printing layer / anchor coating / heat sealing layer (PE)
[0431] (4) Base material layer (CRF) / Printing layer / Anchor coating / Adhesive resin layer (PE) / Heat seal layer (PEF)
[0432] (5) Base material layer (CRF) / printing layer / adhesive layer
[0433] (6) Printing layer / base material layer (CRF) / inorganic thin film layer (Al) / adhesive layer
[0434] (7) Printing layer / base material layer (CRF) / inorganic film layer (Al) / heat sealing layer (PE)
[0435] (8) Printing layer / base material layer (CRF) / inorganic film layer (Al) / anchor coating / heat sealing layer (PE)
[0436] In the examples given here, the base material layer 51 is also a biaxially oriented polyester film 8 .
[0437] (1) Base material layer (CRF) / adhesive layer / metal foil (Al) / adhesive layer / support layer (ONY) / adhesive layer / heat seal layer (PEF)
[0438] (2) Base material layer (CRF) / adhesive layer / metal foil (Al) / adhesive layer / heat seal layer (CPP)
[0439] (3) Base material layer (CRF) / adhesive layer / inorganic thin film layer (Al) / support layer (PET) / adhesive layer / heat sealing layer (PEF)
[0440] (4) Base material layer (CRF) / adhesive layer / support layer (ONY) / adhesive layer / heat seal layer (PEF)
[0441] (5) Base material layer (CRF) / Adhesive layer / Protective layer (MOR) / Inorganic film layer (MO) / Support layer (PET) / Adhesive layer / Heat seal layer (CPP)
[0442] (6) Base material layer (CRF) / adhesive layer / inorganic thin film layer (Al) / support layer (PET) / adhesive layer / heat sealing layer (CPP)
[0443] (7) Base material layer (CRF) / adhesive layer / support layer (ONY) / adhesive layer / metal foil (Al) / adhesive layer / heat sealing layer (CPP)
[0444] (8) Base material layer (CRF) / anchor coating / adhesive resin layer (PE) / metal foil (Al) / heat seal layer (PE)
[0445] (9) Base material layer (CRF) / anchor coating / adhesive resin layer (PE) / metal foil (Al) / anchor coating / heat seal layer (PE)
[0446] (10) Base material layer (CRF) / anchor coating / adhesive resin layer (PE) / inorganic film layer (Al) / support layer (PET) / anchor coating / adhesive resin layer (PE) / heat seal layer (PEF)
[0447] (11) Base material layer (CRF) / anchor coating / adhesive resin layer (PE) / metal foil (Al) / anchor coating / adhesive resin layer (PE) / heat seal layer (PEF)
[0448] (12) Base material layer (CRF) / adhesive layer / support layer (PET) / adhesive layer / heat sealing layer (PEF) / hot melt layer (hot melt adhesive)
[0449] (13) Base material layer (CRF) / inorganic thin film layer (MO) / protective layer (MOR) / adhesive layer / support layer (ONY) / adhesive layer / heat sealing layer (CPP)
[0450] (14) Base material layer (CRF) / inorganic thin film layer (MO) / protective layer (MOR) / adhesive layer / support layer (ONY) / adhesive layer / heat sealing layer (PEF)
[0451] (15) Base material layer (CRF) / inorganic film layer (MO) / protective layer (MOR) / adhesive layer / protective layer (MOR) / inorganic film layer (MO) / support layer (PET) / adhesive layer / heat sealing layer (CPP)
[0452] (16) Base material layer (CRF) / inorganic film layer (MO) / protective layer (MOR) / adhesive layer / inorganic film layer (Al) / support layer (PET) / adhesive layer / heat sealing layer (CPP)
[0453] (17) Base material layer (CRF) / inorganic thin film layer (MO) / protective layer (MOR) / adhesive layer / support layer (ONY) / adhesive layer / metal foil (Al) / adhesive layer / heat sealing layer (CPP)
[0454] (18) Base material layer (CRF) / inorganic film layer (MO) / protective layer (MOR) / adhesive layer / support layer (PET) / adhesive layer / heat seal layer (PEF) / hot melt layer (hot melt adhesive)
[0455] (19) Heat seal layer (PEF) / adhesive layer / base material layer (CRF) / adhesive layer / metal foil (Al) / adhesive layer / heat seal layer (PEF)
[0456] (20) Heat sealing layer (PEF) / adhesive layer / protective layer (MOR) / inorganic film layer (MO) / base material layer (CRF) / adhesive layer / heat sealing layer (PEF)
[0457] (21) Heat seal layer (PE) / base material layer (CRF) / adhesive layer / support layer (PEF) / adhesive layer / metal foil (Al) / adhesive layer / heat seal layer (PEF)
[0458] (22) Heat seal layer (PEF) / adhesive layer / base material layer (CRF) / adhesive layer / support layer (PEF) / adhesive layer / support layer (PET) / inorganic film layer (MO) / protective layer (MOR) / adhesive layer / heat seal layer (PEF)
[0459] (23) Heat seal layer (PEF) / adhesive layer / base material layer (CRF) / adhesive layer / support layer (PEF) / adhesive layer / protective layer (MOR) / inorganic film layer (MO) / support layer (PET) / adhesive layer / heat seal layer (PEF)
[0460] In the examples given here, the base material layer 51 is also a biaxially oriented polyester film 8 .
[0461] (1) Base material layer (CRF) / Printing layer / Adhesive layer / Metal foil (Al) / Adhesive layer / Support layer (ONY) / Adhesive layer / Heat seal layer (PEF)
[0462] (2) Base material layer (CRF) / Printing layer / Adhesive layer / Metal foil (Al) / Adhesive layer / Heat seal layer (CPP)
[0463] (3) Base material layer (CRF) / Printing layer / Adhesive layer / Inorganic thin film layer (Al) / Support layer (PET) / Adhesive layer / Heat seal layer (PEF)
[0464] (4) Base material layer (CRF) / printing layer / adhesive layer / support layer (ONY) / adhesive layer / heat sealing layer (PEF)
[0465] (5) Base material layer (CRF) / Printing layer / Adhesive layer / Protective layer (MOR) / Inorganic film layer (MO) / Support layer (PET) / Adhesive layer / Heat seal layer (CPP)
[0466] (6) Base material layer (CRF) / Printing layer / Adhesive layer / Inorganic film layer (Al) / Support layer (PET) / Adhesive layer / Heat seal layer (CPP)
[0467] (7) Base material layer (CRF) / printing layer / adhesive layer / support layer (ONY) / adhesive layer / metal foil (Al) / adhesive layer / heat sealing layer (CPP)
[0468] (8) Base material layer (CRF) / Printing layer / Anchor coating / Adhesive resin layer (PE) / Metal foil (Al) / Heat seal layer (PE)
[0469] (9) Base material layer (CRF) / Printing layer / Anchor coating / Adhesive resin layer (PE) / Metal foil (Al) / Anchor coating / Heat seal layer (PE)
[0470] (10) Base material layer (CRF) / Printing layer / Anchor coating / Adhesive resin layer (PE) / Inorganic film layer (Al) / Support layer (PET) / Anchor coating / Adhesive resin layer (PE) / Heat seal layer (PEF)
[0471] (11) Base material layer (CRF) / Printing layer / Anchor coating / Adhesive resin layer (PE) / Metal foil (Al) / Anchor coating / Adhesive resin layer (PE) / Heat seal layer (PEF)
[0472] (12) Base material layer (CRF) / Printing layer / Adhesive layer / Support layer (PET) / Adhesive layer / Heat seal layer (PEF) / Hot melt layer (hot melt adhesive)
[0473] (13) Heat seal layer (PEF) / adhesive layer / base material layer (CRF) / printing layer / adhesive layer / metal foil (Al) / adhesive layer / heat seal layer (PEF)
[0474] (14) Heat sealing layer (PEF) / adhesive layer / protective layer (MOR) / inorganic film layer (MO) / base material layer (CRF) / printing layer / adhesive layer / heat sealing layer (PEF)
[0475] (15) Heat seal layer (PE) / base material layer (CRF) / printing layer / adhesive layer / support layer (PEF) / adhesive layer / metal foil (Al) / adhesive layer / heat seal layer (PEF)
[0476] (16) Heat seal layer (PEF) / adhesive layer / base material layer (CRF) / printing layer / adhesive layer / support layer (PEF) / adhesive layer / support layer (PET) / inorganic film layer (MO) / protective layer (MOR) / adhesive layer / heat seal layer (PEF)
[0477] (17) Heat seal layer (PEF) / adhesive layer / base material layer (CRF) / printing layer / adhesive layer / support layer (PEF) / adhesive layer / protective layer (MOR) / inorganic film layer (MO) / support layer (PET) / adhesive layer / heat seal layer (PEF)
[0478] In the examples given here, the support layer is a biaxially oriented polyester film 8 .
[0479] (1) Base material layer (paper) / adhesive layer / metal foil (Al) / adhesive layer / support layer (CRF) / adhesive layer / heat seal layer (PVC)
[0480] (2) Base material layer (ONY) / adhesive layer / support layer (CRF) / adhesive layer / metal foil (Al) / adhesive layer / heat seal layer (PEF)
[0481] (3) Base material layer (PET) / inorganic film layer (MO) / protective layer (MOR) / adhesive layer / support layer (CRF) / adhesive layer / heat seal layer (PEF)
[0482] (4) Base material layer (paper) / adhesive layer / support layer (CRF) / adhesive layer / heat seal layer (CPP)
[0483] (5) Base material layer (OPP) / adhesive layer / support layer (CRF) / adhesive layer / heat seal layer (CPP)
[0484] (6) Base material layer (ONY) / adhesive layer / support layer (CRF) / adhesive layer / heat seal layer (CPP)
[0485] (7) Base material layer (PET) / Adhesive layer / Support layer (CRF) / Adhesive layer / Heat seal layer (PEF) / Hot melt layer (hot melt adhesive)
[0486] (8) Base material layer (OPP) / adhesive layer / support layer (CRF) / adhesive layer / heat seal layer (PEF)
[0487] (9) Base material layer (PET) / inorganic film layer (MO) / protective layer (MOR) / adhesive layer / support layer (CRF) / adhesive layer / heat sealing layer (CPP)
[0488] (10) Heat seal layer (PE) / base material layer (paper) / adhesive resin layer (PE) / anchor coating / metal foil (Al) / adhesive layer / support layer (CRF) / anchor coating / adhesive resin layer (PE) / heat seal layer (PEF)
[0489] (11) Base material layer (paper) / adhesive resin layer (PE) / support layer (CRF) / heat seal layer (PE)
[0490] (12) Base material layer (paper) / adhesive resin layer (PE) / support layer (CRF) / anchor coating / heat seal layer (PE)
[0491] (13) Base material layer (OPP) / adhesive layer / support layer (CRF) / adhesive layer / heat seal layer (OPP)
[0492] (14) Base material layer (PET) / adhesive layer / inorganic thin film layer (Al) / support layer (CRF) / adhesive layer / heat sealing layer (PEF)
[0493] (15) Base material layer (ONY) / anchor coating layer / adhesive resin layer (PE) / inorganic film layer (Al) / support layer (CRF) / anchor coating layer / adhesive resin layer (PE) / heat sealing layer (PEF)
[0494] (16) Base material layer (paper) / adhesive layer / protective layer (MOR) / inorganic film layer (MO) / support layer (CRF) / adhesive layer / heat sealing layer (CPP)
[0495] (17) Base material layer (OPP) / adhesive layer / protective layer (MOR) / inorganic film layer (MO) / support layer (CRF) / adhesive layer / heat seal layer (CPP)
[0496] (18) Base material layer (PET) / inorganic film layer (MO) / protective layer (MOR) / adhesive layer / protective layer (MOR) / inorganic film layer (MO) / support layer (CRF) / adhesive layer / heat sealing layer (PEF)
[0497] (19) Base material layer (ONY) / Adhesive layer / Protective layer (MOR) / Inorganic film layer (MO) / Support layer (CRF) / Adhesive layer / Heat seal layer (CPP)
[0498] (20) Base material layer (PET) / Adhesive layer / Protective layer (MOR) / Inorganic film layer (MO) / Support layer (CRF) / Adhesive layer / Heat seal layer (PEF) / Hot melt layer (hot melt adhesive)
[0499] (21) Base material layer (OPP) / Adhesive layer / Protective layer (MOR) / Inorganic film layer (MO) / Support layer (CRF) / Adhesive layer / Heat seal layer (PEF)
[0500] (22) Base material layer (PET) / adhesive layer / protective layer (MOR) / inorganic film layer (MO) / support layer (CRF) / adhesive layer / heat sealing layer (CPP)
[0501] (23) Base material layer (paper) / adhesive resin layer (PE) / protective layer (MOR) / inorganic film layer (MO) / support layer (CRF) / anchor coating / heat seal layer (PE)
[0502] (24) Base material layer (OPP) / adhesive layer / protective layer (MOR) / inorganic film layer (MO) / support layer (CRF) / adhesive layer / heat seal layer (OPP)
[0503] (25) Base material layer (PET) / Adhesive layer / Support layer (CRF) / Heat seal layer (PE)
[0504] (26) Base material layer (PET) / adhesive layer / support layer (CRF) / anchor coating / heat sealing layer (PE)
[0505] (27) Heat seal layer (PE) / base material layer (paper) / adhesive resin layer (PE) / support layer (CRF) / adhesive layer / heat seal layer (PEF)
[0506] (28) Heat seal layer (PE) / base material layer (paper) / adhesive resin layer (PE) / support layer (CRF) / heat seal layer (PE)
[0507] (29) Heat seal layer (PE) / base material layer (paper) / adhesive resin layer (PE) / support layer (CRF) / anchor coating / heat seal layer (PE)
[0508] In the examples given here, the support layer is also a biaxially oriented polyester film 8.
[0509] (1) Printing layer / base material layer (paper) / adhesive layer / metal foil (Al) / adhesive layer / support layer (CRF) / adhesive layer / heat sealing layer (PVC)
[0510] (2) Base material layer (ONY) / Printing layer / Adhesive layer / Support layer (CRF) / Adhesive layer / Metal foil (Al) / Adhesive layer / Heat seal layer (PEF)
[0511] (3) Printing layer / base material layer (paper) / adhesive layer / support layer (CRF) / adhesive layer / heat sealing layer (CPP)
[0512] (4) Base material layer (OPP) / Printing layer / Adhesive layer / Support layer (CRF) / Adhesive layer / Heat seal layer (CPP)
[0513] (5) Base material layer (ONY) / Printing layer / Adhesive layer / Support layer (CRF) / Adhesive layer / Heat seal layer (CPP)
[0514] (6) Base material layer (PET) / Printing layer / Adhesive layer / Support layer (CRF) / Adhesive layer / Heat seal layer (PEF) / Hot melt layer (hot melt adhesive)
[0515] (7) Base material layer (OPP) / Printing layer / Adhesive layer / Support layer (CRF) / Adhesive layer / Heat seal layer (PEF)
[0516] (8) Heat seal layer (PE) / Printing layer / Base material layer (paper) / Adhesive resin layer (PE) / Anchor coating / Metal foil (Al) / Adhesive layer / Support layer (CRF) / Anchor coating / Adhesive resin layer (PE) / Heat seal layer (PEF)
[0517] (9) Printing layer / base material layer (paper) / adhesive resin layer (PE) / support layer (CRF) / heat sealing layer (PE)
[0518] (10) Printing layer / base material layer (paper) / adhesive resin layer (PE) / support layer (CRF) / anchor coating layer / heat sealing layer (PE)
[0519] (11) Base material layer (OPP) / adhesive layer / support layer (CRF) / printing layer / adhesive layer / heat sealing layer (OPP)
[0520] (12) Base material layer (PET) / Printing layer / Adhesive layer / Inorganic thin film layer (Al) / Support layer (CRF) / Adhesive layer / Heat seal layer (PEF)
[0521] (13) Base material layer (ONY) / Printing layer / Anchor coating / Adhesive resin layer (PE) / Inorganic film layer (Al) / Support layer (CRF) / Anchor coating / Adhesive resin layer (PE) / Heat seal layer (PEF)
[0522] (14) Printing layer / base material layer (paper) / adhesive layer / protective layer (MOR) / inorganic film layer (MO) / support layer (CRF) / adhesive layer / heat sealing layer (CPP)
[0523] (15) Base material layer (OPP) / Printing layer / Adhesive layer / Protective layer (MOR) / Inorganic film layer (MO) / Support layer (CRF) / Adhesive layer / Heat seal layer (CPP)
[0524] (16) Base material layer (ONY) / Printing layer / Adhesive layer / Protective layer (MOR) / Inorganic film layer (MO) / Support layer (CRF) / Adhesive layer / Heat seal layer (CPP)
[0525] (17) Base material layer (PET) / Printing layer / Adhesive layer / Protective layer (MOR) / Inorganic film layer (MO) / Support layer (CRF) / Adhesive layer / Heat seal layer (PEF) / Hot melt layer (hot melt adhesive)
[0526] (18) Base material layer (OPP) / Printing layer / Adhesive layer / Protective layer (MOR) / Inorganic film layer (MO) / Support layer (CRF) / Adhesive layer / Heat seal layer (PEF)
[0527] (19) Base material layer (PET) / Printing layer / Adhesive layer / Protective layer (MOR) / Inorganic film layer (MO) / Support layer (CRF) / Adhesive layer / Heat seal layer (CPP)
[0528] (20) Printing layer / base material layer (paper) / adhesive resin layer (PE) / protective layer (MOR) / inorganic film layer (MO) / support layer (CRF) / heat sealing layer (PE)
[0529] (21) Printing layer / base material layer (paper) / adhesive resin layer (PE) / protective layer (MOR) / inorganic film layer (MO) / support layer (CRF) / anchor coating layer / heat sealing layer (PE)
[0530] (22) Base material layer (OPP) / Printing layer / Adhesive layer / Protective layer (MOR) / Inorganic film layer (MO) / Support layer (CRF) / Adhesive layer / Heat seal layer (OPP)
[0531] (23) Base material layer (PET) / Adhesive layer / Printing layer / Support layer (CRF) / Heat seal layer (PE)
[0532] (24) Base material layer (PET) / Printing layer / Adhesive layer / Support layer (CRF) / Heat seal layer (PE)
[0533] (25) Base material layer (PET) / adhesive layer / printing layer / support layer (CRF) / anchor coating / heat sealing layer (PE)
[0534] (26) Base material layer (PET) / Printing layer / Adhesive layer / Support layer (CRF) / Anchor coating / Heat seal layer (PE)
[0535] (27) Heat seal layer (PE) / Printing layer / Base material layer (paper) / Adhesive resin layer (PE) / Support layer (CRF) / Adhesive layer / Heat seal layer (PEF)
[0536] (28) Heat seal layer (PE) / Printing layer / Base material layer (paper) / Adhesive resin layer (PE) / Support layer (CRF) / Heat seal layer (PE)
[0537] (29) Heat seal layer (PE) / Printing layer / Base material layer (paper) / Adhesive resin layer (PE) / Support layer (CRF) / Anchor coating / Heat seal layer (PE)
[0538] In the above specific examples, there are some laminated bodies 9 in which the base layer 51 is adjacent to the inorganic thin film layer 31. In these laminated bodies 9, the anchor coating layer 32 may be provided between the base layer 51 and the inorganic thin film layer 31.
[0539] In the above-mentioned specific examples, there are some laminated bodies 9 in which the support layer is adjacent to the inorganic thin film layer 31. In these laminated bodies 9, an anchor coating layer 32 may be provided between the support layer and the inorganic thin film layer 31.
[0540] Among the above-mentioned specific examples, there are some laminated bodies 9 including a protective layer 33 formed of a composition containing MOR, that is, a metal alkoxide. In these laminated bodies 9, the protective layer 33 may be formed of a composition containing a resin and a curing agent.
[0541] In the above specific examples, there are some laminated bodies 9 including both the base material layer 51 and the support layer. In these examples, both the base material layer 51 and the support layer may be the biaxially oriented polyester film 8 .
[0542] The laminate 9 can be used for various purposes. For example, it can be suitably used as a packaging container, a label (e.g., a label for a PET plastic bottle), and a film for outer packaging of electronic components, including the outer packaging of lithium ion batteries. Among them, it can be suitably used for packaging containers. It can be particularly suitably used for food packaging containers.
[0543] <4. Packaging Container>
[0544] The packaging container of the present embodiment includes a laminate 9. That is, the packaging container of the present embodiment can be made using the laminate 9. Here, "the packaging container includes a laminate 9" means that when the packaging container is composed of a plurality of components, at least one component includes the laminate 9. As the packaging container, for example, packaging bags (i.e., soft bags), lid materials, laminated tubes, paper containers, paper cups (for example, refer to Japanese Patent Gazette No. 6984717) can be listed. The packaging container can be a food packaging container or a non-food packaging container. In other words, the contents can be food or non-food. Among them, the packaging container is preferably a food packaging container.
[0545] Examples of packaging bags include stand-up bags, pillow bags (i.e., butt-sealed bags), two-side sealed bags, three-side sealed bags, four-side sealed bags, side sealed bags, envelope sealed bags, pleat sealed bags, flat bottom sealed bags, square bottom sealed bags, and bags with gussets.
[0546] <5. Various changes may be made to the above-mentioned embodiments>
[0547] Various modifications may be made to the above-described embodiment. For example, one or more modifications may be selected from the following modified examples to modify the above-described embodiment.
[0548] In the above embodiment, the biaxially oriented polyester film 8 is described as a three-layer structure consisting of the first layer 81, the second layer 82 and the third layer 83. However, the above embodiment is not limited to this structure. The biaxially oriented polyester film 8 may be a single-layer structure, or a two-layer structure consisting of the first layer 81 and the second layer 82. Of course, the biaxially oriented polyester film 8 may be a structure with four or more layers.
[0549] Example
[0550] The present invention is described in more detail below by way of examples and comparative examples. In the following, unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass". It should be noted that the polyesters A to G described below are sometimes collectively referred to as raw material polyesters.
[0551] <Methods for measuring various physical properties>
[0552] (Intrinsic viscosity)
[0553] 0.2 g of a sample (specifically, a raw material polyester and a biaxially oriented polyester film) was dissolved in 50 ml of a mixed solvent of phenol / 1,1,2,2-tetrachloroethane (60 / 40 (mass ratio)), and the intrinsic viscosity (IV) was measured using an Ostwald viscometer at 30° C. The unit of the intrinsic viscosity is dl / g.
[0554] (Content ratio of terephthalic acid component and isophthalic acid component)
[0555] The sample (specifically, the raw material polyester and the biaxially oriented polyester film) was dissolved in a solvent obtained by mixing chloroform D (manufactured by Yurichup Co., Ltd.) and trifluoroacetic acid-D1 (manufactured by Yurichup Co., Ltd.) at a volume ratio of 10:1. The NMR of the proton was measured for the sample solution using a nuclear magnetic resonance (NMR) spectrometer ("GEMINI-200", manufactured by Varian) under the measurement conditions of a temperature of 23° C. and a cumulative number of 64 times. In the NMR measurement, the content (mol %) of the terephthalic acid component and the isophthalic acid component in 100 mol % of the acid component was calculated based on the calculated peak intensity of the predetermined proton.
[0556] (Quantitative analysis of magnesium)
[0557] The sample (specifically, the raw material polyester and the biaxially oriented polyester film) was ashed and decomposed in a platinum crucible, and 6 mol / L hydrochloric acid was added and evaporated to dryness. It was dissolved with 1.2 mol / L hydrochloric acid, and magnesium was quantified using an inductively coupled plasma (ICP) emission spectrometer ("ICPS-2000" manufactured by Shimadzu Corporation).
[0558] (Quantitative analysis of phosphorus)
[0559] Phosphorus is converted into orthophosphoric acid by a method of dry incineration decomposition of a sample (specifically, a raw material polyester and a biaxially oriented polyester film) in the presence of sodium carbonate or a method of wet decomposition using any of a sulfuric acid, nitric acid, perchloric acid system and a sulfuric acid, hydrogen peroxide aqueous system. Subsequently, molybdate is reacted in a 1 mol / L sulfuric acid solution to produce phosphomolybdic acid, which is reduced with hydrazine sulfate, and the absorbance at 830 nm of the heteropoly blue thus produced is measured using an absorptiophotometer ("UV-150-02" manufactured by Shimadzu Corporation) (in other words, colorimetric quantification is performed).
[0560] (Melting resistivity)
[0561] The sample (specifically, the raw material polyester and the biaxially oriented polyester film) was melted at 285° C., a pair of electrode plates were inserted therein, and a voltage of 120 V was applied. The current at this time was measured, and the melt resistivity Si (Ω·cm) was calculated according to the following formula.
[0562] Si=(A / I)×(V / io)
[0563] Here, A is the area of the electrode (cm 2 ), I is the distance between electrodes (cm), V is the voltage (V), and io is the current (A).
[0564] (Area ratio of the region with molecular weight of 1000 or less)
[0565] 10 g of the sample (specifically, the raw polyester and the biaxially oriented polyester film) is placed in a 30 mL vial and weighed. A mixed solution of chloroform / HFIP = 98 / 2 (volume ratio) is added to the vial and allowed to stand for 12 hours to dissolve the sample. Next, it is diluted with chloroform / hexafluoroisopropanol (HFIP) = 98 / 2 (volume ratio) to prepare a 0.1% solution. The 0.1% solution is filtered with a 0.45 μm filter (manufactured by GL SCIENCES, GL chromatographic disk non-aqueous N type 13N). For the filtrate, gel permeation chromatography (GPC) measurement is performed according to the following conditions.
[0566] Column used: Tosoh Corporation, TSKgel SuperHM-H×2 and TSKgel SuperH2000
[0567] Column temperature: 40°C
[0568] Mobile phase: Chloroform / HFIP=98 / 2 (volume ratio)
[0569] Flow rate: 0.6mL / min
[0570] Injection volume: 20 μL
[0571] Detection: 254nm (UV-visible detector)
[0572] Molecular weight calibration: Monodisperse polystyrene (manufactured by Tosoh Corporation)
[0573] Device: Made by Tosoh Corporation, HLC-8300GPC
[0574] In the molecular weight distribution curve obtained by GPC measurement, the area ratio of the region with a molecular weight of 1,000 or less was determined.
[0575] It should be noted that, usually in GPC analysis, the area outside the range of the standard curve usually deviates from the calculation range of the GPC analysis. However, in this analysis, in order to more accurately determine the area ratio of the region with a molecular weight of less than 1000, the GPC chromatographic area (i.e., the total peak area) was calculated not only within the range of the standard curve but also outside the range of the standard curve.
[0576] (thickness)
[0577] The thickness of the biaxially oriented polyester film was measured using a micrometer in accordance with JIS K7130-1999 A method.
[0578] (Melting Point)
[0579] 5 mg of the sample (specifically, a biaxially oriented polyester film) was heated from 25°C to 320°C at 10°C / min using a differential scanning calorimeter (DSC60 manufactured by Shimadzu Corporation) to determine the main peak top temperature of the endothermic curve associated with melting as the melting point.
[0580] (Tensile Strength)
[0581] A test piece of 15 mm wide and 100 mm long was cut from the biaxially oriented polyester film. According to JIS K 7127, the test piece was stretched using a tensile testing machine ("Autograph AG-I" manufactured by Shimadzu Corporation) at a distance of 50 mm between markings and a stretching speed of 200 mm / min. The tensile strength, i.e., tensile strength at break, of the test piece was calculated based on the stress / strain curve obtained thereby. The tensile strengths in the MD (i.e., 0° direction), 45° direction, TD (i.e., 90° direction), and 135° direction were determined according to this procedure.
[0582] (Heat shrinkage)
[0583] A test piece with a width of 10 mm and a length of 250 mm was cut from the biaxially oriented polyester film. A pair of marks (i.e., a pair of marking lines) were marked at intervals of 200 mm along the length direction of the test piece, and the distance between the marking lines was measured under a tension of 5 gf. The test piece was heated at 150°C for 30 minutes under no load, and the distance between the marking lines was measured. Based on their measurement results, the heat shrinkage rate was calculated using the following formula.
[0584] Thermal shrinkage (%) = {(AB) / A} × 100
[0585] Here, A is the distance between the marking lines before the heat treatment, and B is the distance between the marking lines before the heat treatment.
[0586] According to this procedure, the heat shrinkage rates in MD and TD were calculated.
[0587] (Color b * value)
[0588] Ten biaxially oriented polyester films were stacked and placed on a colorimeter ("ZE2000" manufactured by Nippon Denshoku Industries Co., Ltd.), and the color b was determined by the reflection method. * The color b per 1 μm thickness is calculated using the following formula: * value.
[0589] Color b per 1μm thickness * value
[0590] =(Color b when 10 biaxially oriented polyester films are stacked * value) / (10×thickness of biaxially oriented polyester film)
[0591] (Surface crystallinity)
[0592] The FT-IR ATR measurement was performed on both the corona-treated surface and the non-treated surface of the biaxially oriented polyester film under the following conditions: That is, a spectrum was obtained by using a Fourier transform infrared spectrophotometer and a total reflection attenuation method.
[0593] FT-IR: Bio Rad DIGILAB, FTS-60A / 896
[0594] Single reflection ATR accessories: golden gate MKII (made by SPECAC)
[0595] Internal reflective element: Diamond
[0596] Angle of incidence: 45°
[0597] Resolution: 4cm -1
[0598] Cumulative times: 128 times
[0599] The surface crystallinity is determined by the -1 The absorption near 1410 cm -1 The intensity of the absorption near (1340cm -1 Strength / 1410cm -1 The intensity of -1 The absorption near 1410 cm is due to the absorption of the angular vibration of CH2 (trans structure) of ethylene glycol. -1 The absorption appearing nearby is absorption that has nothing to do with crystallinity and orientation.
[0600] (Puncture Strength)
[0601] The puncture strength of a 5 cm square test piece cut out from a biaxially oriented polyester film was measured in accordance with JIS Z 1707 using a digital dynamometer ("ZTS-500N" manufactured by IMADA Co., Ltd.), an electric measuring test stand ("MX2-500N" manufactured by IMADA Co., Ltd.), and a jig for film puncture testing ("TKS-250N" manufactured by IMADA Co., Ltd.). From the puncture strength obtained by the measurement (i.e., the puncture strength of the biaxially oriented polyester film), the puncture strength per 1 μm thickness was also calculated.
[0602] (Lamination Strength)
[0603] A urethane two-component curing adhesive (specifically, an adhesive obtained by mixing "TAKELAC (registered trademark) A525S" manufactured by Mitsui Chemicals, Inc. and "TAKENATE (registered trademark) A50" manufactured by Mitsui Chemicals, Inc. at a ratio of 13.5:1 (mass ratio)) was used, and an unstretched polypropylene film ("P1147" manufactured by Toyobo Co., Ltd.) with a thickness of 70 μm as a polyolefin sealant layer was adhered to the corona-treated surface side of the biaxially oriented polyester film by dry lamination, and aging was performed at 40° C. for 4 days to prepare a laminate according to the above steps. For a test piece with a width of 15 mm and a length of 200 mm cut out from the laminate, the peel strength (N / 15 mm) of the bonding surface between the corona-treated surface of the biaxially oriented polyester film and the polyolefin resin layer was measured. The peel strength was measured at a temperature of 23° C. and a relative humidity of 65% using “TENSILON UMT-II-500” manufactured by TOYO BALDWIN CO., LTD., at a tensile speed of 20 cm / min and a peel angle of 180 degrees.
[0604] (Maximum casting speed)
[0605] The unstretched film produced while changing the rotation speed of the cooling drum stepwise was visually checked for the presence of needle bubbles using a polarizing plate (manufactured by Nishida Industries, Ltd.) Thus, the maximum casting speed was determined from the maximum rotation speed at which needle bubbles were not generated.
[0606] (Film-forming properties)
[0607] The film forming properties of the biaxially oriented polyester film were evaluated according to the following criteria.
[0608] ○: No breakage for 60 minutes or more. That is, continuous film formation was possible for 60 minutes or more.
[0609] △: The film was broken at least once within a period of 30 minutes or more and less than 60 minutes.
[0610] ×: Broken at least once in less than 30 minutes.
[0611] <Raw material polyester>
[0612] (Polyester B)
[0613] The bundle of PET plastic bottles that have been collected and recycled is pulverized while circulating in a wet grinder together with a cleaning solution (specifically, a cleaning solution obtained by adding 500 g of liquid kitchen detergent to 1000 liters of water). A gravity separator connected to the wet grinder is used to precipitate foreign matter with a high specific gravity such as metal, sand, and glass, and flakes are taken out from the upper layer. The flakes are rinsed with pure water and centrifuged for dehydration. Recycled flakes are obtained by following this procedure.
[0614] 30 kg of the recovered flakes melted in an undried state and a preheated mixed solution, specifically a mixed solution of 150 kg of ethylene glycol and 150 g of zinc acetate dihydrate, were mixed in a stirring autoclave, and fractions having a lower boiling point than ethylene glycol, such as water and acetic acid, were removed. Then, the mixture was reacted at a temperature of 195° C. to 200° C. for 4 hours using a reflux condenser.
[0615] After the reaction was completed, the temperature of the reactor contents was lowered until the temperature reached 97° C. to 98° C., and the contents were filtered while hot to remove suspended matter and precipitate.
[0616] The filtrate was further cooled, and after confirming that the crude BHET had completely dissolved, the filtrate was passed through an activated carbon bed and then an anion / cation exchange mixed bed at 50° C. to 51° C. for 30 minutes. In other words, a pre-purification treatment was performed.
[0617] The pre-purification treatment liquid was placed in a stirring autoclave and heated to distill off the remaining ethylene glycol under normal pressure, thereby obtaining a BHET-concentrated melt.
[0618] The melt of concentrated BHET was stirred in a nitrogen atmosphere and naturally cooled, and then taken out from the stirring autoclave to obtain fine flakes of concentrated BHET.
[0619] The fine pieces were heated to 130° C. to be melted, and then supplied to a thin-film vacuum evaporator by a metering pump to be evaporated and cooled to be condensed, thereby obtaining purified BHET.
[0620] 2650 kg of the refined BHET was supplied to a dissolving tank replaced with nitrogen at one time, and after nitrogen replacement again, the temperature of the dissolving tank was set to 150°C for dissolution. After the dissolution was completed, the temperature of the dissolving tank was raised to 230°C over 30 minutes while stirring. 2650 kg of the obtained BHET solution was transferred to a polycondensation reaction tank, and 300 ppm of antimony trioxide, 170 ppm of cobalt acetate, 55 ppm of phosphoric acid, and 0.3 wt% of titanium dioxide were added to the BHET solution relative to the amount of PET obtained (about 2000 kg of PET can be obtained from 2650 kg of BHET), and the temperature of the polycondensation reaction tank was slowly raised from 230°C to 290°C while stirring at 10 to 40 rpm, and the pressure was reduced to 40 Pa. After reaching a predetermined stirring torque, the polycondensation reaction vessel was purged with nitrogen and returned to normal pressure to stop the polycondensation reaction, and the strands were ejected and cooled, and then immediately cut to obtain polyester flakes.
[0621] According to this procedure, a chemically recycled polyester, polyester B, having an intrinsic viscosity of 0.59 dl / g was obtained.
[0622] (Polyester A)
[0623] Polyester B (i.e., chemically recycled polyester having an intrinsic viscosity of 0.59 dl / g) was continuously supplied to a crystallization device, crystallized at 150°C, and then supplied to a dryer and dried at 130°C for 10 hours. The dried polyester B was transferred to a preheater, heated to 180°C, and supplied to a solid phase polymerization machine. Solid phase polymerization was performed at 190°C for 24 hours under nitrogen to obtain a chemically recycled polyester having an intrinsic viscosity of 0.79 dl / g, i.e., polyester A.
[0624] (Polyester C)
[0625] A chemically recycled polyester having an intrinsic viscosity of 0.83 dl / g, namely, polyester C, was obtained in the same manner as polyester A except that the time for the solid phase polymerization reaction was changed from 24 hours to 50 hours.
[0626] (Polyester D)
[0627] After washing away foreign matters such as residual beverages from a PET plastic bottle for beverages, the PET plastic bottle for beverages is crushed to obtain flakes. The flakes are mixed into a 3.5% by mass sodium hydroxide solution, stirred at a flake concentration of 10% by mass, 85°C, and 30 minutes, thereby washing (in other words, alkaline washing). Using distilled water, the flakes taken out after the alkaline washing are stirred at a flake concentration of 10% by weight, 25°C, and 20 minutes, thereby washing. For this water washing, the distilled water is replaced each time, and it is further performed 2 times. The washed flakes are dried and melted using an extruder, and passed into a filter to filter out foreign matters. As for the filter, it is arranged in the extruder in such a way that the mesh size becomes smaller in sequence until the third stage filter. The mesh size of the third stage filter is 50μm. According to this procedure, a mechanically recycled polyester with a characteristic viscosity of 0.69dl / g, i.e., polyester D, is obtained.
[0628] (Polyester E)
[0629] As polyester E, i.e., polyester derived from fossil fuel, polyester (manufactured by Toyobo Co., Ltd.) having an intrinsic viscosity of 0.62 dl / g and terephthalic acid / ethylene glycol = 100 mol% / 100 mol% was used. In other words, homopolyethylene terephthalate (i.e., homo-PET) having an intrinsic viscosity of 0.62 dl / g was used. It should be noted that, for the sake of caution, it is stated in advance that terephthalic acid and ethylene glycol are not derived from used polyester products, but are derived from fossil fuels.
[0630] (Polyester F)
[0631] When the temperature of the esterification reaction tank was raised to 200°C, a slurry containing 86.4 parts by mass of terephthalic acid and 64.4 parts by mass of ethylene glycol was added, and 0.017 parts by mass of antimony trioxide and 0.16 parts by mass of triethylamine as catalysts were added while stirring. Then, the temperature was raised and a pressure esterification reaction was carried out at a gauge pressure of 0.34 MPa and 240°C.
[0632] Thereafter, the esterification reaction tank was restored to normal pressure, and 0.071 parts by mass of magnesium acetate tetrahydrate was added, followed by 0.014 parts by mass of trimethyl phosphate. After heating to 260°C for 15 minutes, 0.012 parts by mass of trimethyl phosphate was added, followed by 0.0036 parts by mass of sodium acetate. 15 minutes after the addition of these, 3.0 parts by mass of ethylene glycol slurry of irregularly shaped silica particles with an average particle size of 2.7 μm was added based on the particle content. The obtained esterification reaction product was transferred to a polycondensation reaction tank, and a polycondensation reaction was carried out at 280°C under reduced pressure to obtain a polyester F having an intrinsic viscosity of 0.61 dl / g.
[0633] Here, the ethylene glycol slurry of irregular shaped silica particles is obtained by mixing irregular shaped silica particles in ethylene glycol, dispersing the mixture using a high pressure disperser, removing 35% of coarse particles by centrifugation, and filtering the mixture using a metal filter with a mesh size of 5 μm.
[0634] It should be noted that, for the sake of caution, it is stated in advance that terephthalic acid and ethylene glycol are not derived from used polyester products, but are substances derived from fossil fuels.
[0635] (Polyester G)
[0636] When the temperature of the esterification reaction tank was raised to 200°C, a slurry containing 86.4 parts by mass of terephthalic acid and 64.4 parts by mass of ethylene glycol was added, and 0.025 parts by mass of antimony trioxide and 0.16 parts by mass of triethylamine as catalysts were added while stirring. Then, the temperature was raised and a pressure esterification reaction was carried out at a gauge pressure of 0.34 MPa and 240°C.
[0637] Thereafter, the esterification reaction tank was restored to normal pressure, and 0.34 parts by mass of magnesium acetate tetrahydrate was added, followed by 0.042 parts by mass of trimethyl phosphate. After heating to 260°C in 15 minutes, 0.036 parts by mass of trimethyl phosphate was added, followed by 0.0036 parts by mass of sodium acetate. The obtained esterification reaction product was transferred to a polycondensation reaction tank, and after slowly heating from 260°C to 280°C under reduced pressure, a polycondensation reaction was carried out at 285°C. After the polycondensation reaction was completed, a filter made of a stainless steel sintered system with a pore size of 5μm (initial filtration efficiency of 95%) was used for filtration treatment to obtain a polyester G with an intrinsic viscosity of 0.62dl / g. It should be noted that, for the sake of caution, it is stated in advance that terephthalic acid and ethylene glycol are not derived from used polyester products, but are substances derived from fossil fuels.
[0638] [Table 1]
[0639]
[0640] Supplementary explanation is given for Table 1. TPA is the abbreviation for terephthalic acid. EG is the abbreviation for ethylene glycol. IPA is the abbreviation for isophthalic acid.
[0641] In the columns of TPA, EG and IPA, "-" means not determined.
[0642] Mg represents the content of magnesium compound based on magnesium atoms. This content is the mass of magnesium compound based on magnesium atoms relative to the mass of polyester (in other words, the mass of magnesium compound based on magnesium atoms / the mass of polyester). It should be noted that here, among the alkaline earth metal compounds, only the content of magnesium compound is shown. This is because the raw material polyester does not contain alkaline earth metal compounds other than magnesium compounds (it can also be said that it is less than the detection limit).
[0643] P represents the content of the phosphorus compound based on phosphorus atoms. This content is the mass of the phosphorus compound based on phosphorus atoms relative to the mass of the polyester (in other words, the mass of the phosphorus compound based on phosphorus atoms / the mass of the polyester).
[0644] As shown in Table 1, among polyesters A, B and C, polyester C has the highest intrinsic viscosity and the least low molecular weight components. Polyester B has the lowest intrinsic viscosity and the most low molecular weight components. In other words, the higher the intrinsic viscosity, the lower the content of low molecular weight components.
[0645] The intrinsic viscosity of polyester B (ie, chemically recycled polyester) is lower than that of polyester E (ie, polyester derived from fossil fuels), and the content of low molecular weight components is about the same as that of polyester E.
[0646] On the other hand, the intrinsic viscosity of polyester D (ie, mechanically recycled polyester) is higher than that of polyester E (ie, polyester derived from fossil fuels), and the content of low molecular weight components is also higher than that of polyester E.
[0647] <Example 1>
[0648] Three extruders were used to produce a three-layer biaxially oriented polyester film. To form the base layer, i.e., layer B, of the biaxially oriented polyester film, 50.0% by mass of polyester A, 42.0% by mass of polyester E, and 8.0% by mass of polyester G were used. On the other hand, to form a pair of surface layers, i.e., a pair of A layers, of the biaxially oriented polyester film, 50.0% by mass of polyester A, 39.0% by mass of polyester E, 3.0% by mass of polyester F, and 8.0% by mass of polyester G were used. The following is a description of the film-making process.
[0649] The raw polyester used to form the A layer is dried and supplied to the first extruder and the third extruder to be melted at 285°C. The raw polyester used to form the B layer is dried and supplied to the second extruder to be melted at 285°C. The molten polyester is introduced from each extruder into the T die, and is stacked in the T die in the form of A layer / B layer / A layer (thickness of 1μm / 10μm / 1μm), and extruded from the T die, and cooled and solidified by a casting cylinder, i.e., a cooling cylinder, whose surface temperature is 25°C. At this time, a lead-shaped electrode with a diameter of 0.15mm is used to charge the film before it is extruded from the T die and tightly fitted with the cooling cylinder. The casting speed is 70m / minute. An unstretched film is produced according to this procedure.
[0650] The unstretched film was heated to 120° C. using an infrared heater and stretched in one step in the longitudinal direction (ie, MD) at a stretch ratio of 4.0 times.
[0651] Next, the film was stretched in the width direction (i.e., TD) using a tenter-type transverse stretching machine under the conditions of a preheating temperature of 120°C, a stretching temperature of 130°C, and a stretching ratio of 4.2, and then heat-set at 245°C and 5% heat-relaxed in the width direction. It should be noted that the length of the width-direction stretching zone was 12.2 m, and the width-direction stretching speed (i.e., TD stretching ratio) was 122.66% / sec. Next, in a pair of A layers, the film was stretched at 40 W·min / m 2 The A layer in contact with the cooling cylinder is subjected to corona treatment under the condition of , and is wound into a roll using a winder.
[0652] According to the above procedure, a mother roll (roll length: 60000 m, width: 8000 mm) of a biaxially oriented polyester film having a thickness of 12 μm was obtained.
[0653] The biaxially oriented polyester film was unwound from the mother roll, cut into 800 mm widths, and rolled into a roll on a core having a diameter of 6 inches (152.2 mm) while applying surface pressure with a touch roller and tension with a biaxial turret winder.
[0654] According to this procedure, a biaxially oriented polyester film is obtained.
[0655] <Examples 2 to 5 and Comparative Examples 1 to 3>
[0656] The biaxially oriented polyester film was prepared in the same manner as in Example 1 except that the mixing ratio of the raw polyester and the film-forming conditions were changed according to the ratio in Table 2. It should be noted that the casting speed was 70 m / min in all of these examples. In all of these examples, the length of the width direction stretching zone was 12.2 m, and the width direction stretching speed (i.e., TD stretching ratio) was 122.66% / sec.
[0657] <Example 6>
[0658] An unstretched film was obtained in the same manner as in Example 1 except that the mixing ratio of the raw material polyester was changed according to the compounding ratio in Table 2. The casting speed was 70 m / min.
[0659] The ends of the unstretched film were gripped by the clamps of a tenter-type simultaneous biaxial stretching machine, and after running in a preheating zone at 120°C, simultaneous biaxial stretching was performed at 130°C, 4.0 times in the longitudinal direction (i.e., MD), and 4.2 times in the width direction (i.e., TD). Next, the relaxation rate in the width direction was set to 5%, and after heat treatment at a temperature of 245°C, the film was cooled to room temperature and wound up to obtain a biaxially oriented polyester film with a thickness of 12 μm.
[0660] [Table 2]
[0661]
[0662] Supplementary explanation is given for Table 2. The "mixing ratio" recorded in Table 2 is expressed as a value when the total mass of the raw material polyester used to form the target layer is set to 100 mass%. For example, it is expressed as follows: for the B layer of Example 1, the polyester A accounts for 50 mass% of the total mass of the polyesters A, E and G used to form the B layer, which is 100 mass%.
[0663] The silica content is the mass of silica relative to the mass of the target layer (in other words, the mass of silica / the mass of the target layer). The mass of the target layer refers to the total mass of the raw materials (e.g., polyester, pellets) used to form the target layer. "CRPET" is a general term for polyesters A, B, and C.
[0664] Mg represents the content of the magnesium compound based on magnesium atoms. This content is the mass of the magnesium compound based on magnesium atoms relative to the mass of the biaxially oriented polyester film.
[0665] P represents the content of the phosphorus compound based on phosphorus atoms. This content is the mass of the phosphorus compound based on phosphorus atoms relative to the mass of the biaxially oriented polyester film.
[0666] By replacing 50% by mass of polyester E (i.e., polyester derived from fossil fuels) with polyester D (i.e., mechanically recycled polyester), the content of low molecular weight components becomes too high, and the color of the biaxially oriented polyester film is changed. * The value also becomes too high (refer to Comparative Examples 1 and 2).
[0667] By replacing 80% by mass of polyester E (i.e., polyester derived from fossil fuels) with polyester C (i.e., chemically recycled polyester having an intrinsic viscosity of 0.83 dl / g), the intrinsic viscosity became too high and the content of low molecular weight components became too low. Furthermore, the film broke during stretching (see Comparative Examples 1 and 3).
[0668] On the other hand, by replacing a certain amount (specifically 50 mass %, 20 mass %, 80 mass %) of polyester E with polyester A (i.e., chemically recycled polyester having an intrinsic viscosity of 0.79 dl / g), a biaxially oriented polyester film can be produced without breaking and the color b can be suppressed. * Value (see Comparative Example 1 and Examples 1 to 3). Even in the case of simultaneous biaxial stretching, a biaxially oriented polyester film can be produced without breaking (see Example 6).
[0669] By replacing a certain amount of polyester E (specifically 50 mass %, 80 mass %) with polyester B (i.e., chemically recycled polyester having an intrinsic viscosity of 0.59 dl / g), a biaxially oriented polyester film can be produced without breaking and the color b can be suppressed. * Value (refer to Comparative Example 1 and Examples 4 and 5).
[0670] Industrial Applicability
[0671] The present invention relates to a biaxially oriented polyester film, and therefore, the present invention has industrial applicability.
[0672] Description of Reference Numerals
[0673] 8...biaxially oriented polyester film, 81...first layer, 82...second layer, 83...third layer, 9...laminate, 11...printing layer, 21...sealing layer, 22...sealing layer, 31...inorganic thin film layer, 32...anchor coating layer, 33...protective layer, 51...substrate layer, 61...intermediate layer.
Claims
1. A biaxially oriented polyester film comprising chemically recycled polyester, In the molecular weight distribution curve obtained by gel permeation chromatography, the area ratio of the region with a molecular weight of 1,000 or less is 1.9% or more and 5.5% or less of the total peak area.
2. The biaxially oriented polyester film according to claim 1, wherein the color b per 1 μm thickness is * The value is below 0.
067.
3. The biaxially oriented polyester film according to claim 1, wherein The content of the chemically recycled polyester is 20% by mass or more. 4 . A laminate comprising the biaxially oriented polyester film according to claim 1 and a sealing layer.
5. The laminate according to claim 4, further comprising a printing layer, In at least a portion of the laminate, the printed layer, the biaxially oriented polyester film, and the sealant layer are arranged in this order in a thickness direction of the laminate.
6. The laminate according to claim 4, further comprising a printing layer, In at least a portion of the laminate, the biaxially oriented polyester film, the printed layer, and the sealant layer are arranged in this order in a thickness direction of the laminate. 7 . A laminate comprising the biaxially oriented polyester film according to claim 1 and an adhesive layer.
8. The laminate according to claim 7, further comprising a printing layer, In at least a portion of the laminate, the printed layer, the biaxially oriented polyester film, and the adhesive layer are arranged in this order in a thickness direction of the laminate.
9. The laminate according to claim 7, further comprising a printing layer, In at least a portion of the laminate, the biaxially oriented polyester film, the printed layer, and the adhesive layer are arranged in this order in the thickness direction of the laminate. 10 . A packaging container comprising the laminate according to claim 4 .
Citation Information
Patent Citations
Method for cleaning semiconductor substrate
JP1985036099B2
Chemical recycle of polyethylene terephthalate waste
JP2000169623A
Thermal decomposition of polyethylene terephthalate
JP2000302707A